Inhibitor application in organic-amended soils: Amendment-specific effects on cereal productivity and soil gas mitigation - Tengsheng Li; Ping Gong; Xiangxin Sun; Zhanbo Wei; Hao Sun; Kaikuo Wu; Yan Xue; Yuchao Song; Furong Xiao; Qiang Ma; Dongpo Li; Wantai Yu; et al. (Soil and Tillage Research, 2026)

Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Chemical constituents from the fruits of Hypericum patulum and their chemotaxonomic significance - Xue Liu; Jing-Yi Xue; Jian-Ping Yang; Li Jiang; Yang Wang; Xue Ma; Lin Tian; Yong-Jun Li (Biochemical Systematics and Ecology, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Antibiotics affect the water purification performance and greenhouse gases emission mode in modular moving bed constructed wetland - Ping Deng; Hongyun Ma; Zhihao Luo; Lingwei Kong; Lei Zhou; Xueqi Zhang; Jianshi Huang; Yiqian Chen; Yiyang Li; Yuefang He; Shaole Yu; Shuiping Cheng (Chemical Engineering Journal, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

Government subsidy strategy and ship green upgrading decision in coal water transportation - Xiang Li; Xiaoqian Ma; Zhong Du; Changan Li; Zhi-Ping Fan (Ocean & Coastal Management, 2026)

Pretreatment-driven component-oriented conversion and microbial community assembly: Selective regulation of coupled methane and vivianite recovery in anaerobic digestion - Lulu Dai; Shaoyang Ma; Ping Zhang; Xianhong Wang; Bo Dong; Yixin Liu; Weihua Li (Journal of Environmental Chemical Engineering, 2026)

GABA-enriched Lactobacillus buchneri XBMU-C1 fermentation broth lowers blood pressure in L-NAME-induced hypertensive rats via RAAS suppression and PI3K/Akt/eNOS activation - Dandan Gao; Chenchen Wang; Ying Chen; Jiwen Wang; Junyao Mei; Yujie Cao; Xuankang Yang; Shangyun Kang; Jinyong Ma; Ping Li (Food Research International, 2026)

Indian monsoon regulates the sediment supply of the Upper Yangtze River since ∼2 Ma - Xudong Zhao; Taylor F. Schildgen; Huiping Zhang; Weitao Wang; Yan Ma; Ping Wang; Yarong Zhang; Yifei Li; Chaopeng Li; Hongseng Xie; Peizhen Zhang (Earth and Planetary Science Letters, 2026)

Probabilistic modeling of failure mechanisms of sensitive clay slopes with non-stationary heterogeneity - Shui-Hua Jiang; Jian-Ping Li; Guo-Tao Ma; Lu-Lu Zhang; Mohammad Rezania; Mohaddeseh Mousavi Nezhad (Computers and Geotechnics, 2026)

Spatial patterns of phylogenetic diversity and endemism enhance biodiversity conservation in Myanmar - Thant Sin Aung; Xiao-Li Shen; Alice C. Hughes; Ke-Ping Ma (Biological Conservation, 2026)

Setback distances for rectangular foundations subjected to earthquake-induced normal-fault surface rupture: 1 g physical model tests - Jianke Ma; Jianyi Zhang; Ping Li; Haonan Zhang; Yuxin Chen; Tuo Wang; Hongjuan Chen; Tingkai Nian (Bulletin of Earthquake Engineering, 2026)

Balancing color and order: Configuration-dependent effects of dominant color composition and spatial structure on scenic quality in urban forest landscapes - Zuoyou Hu; Ping Li; Zhongyi Li; Jiheng Li; Xianwen Li; Bingqian Ma; Chengyang Xu; Richard J. Hauer (Journal of Environmental Management, 2026)

Chenietains A-G, undescribed phenylpropanoid-related compounds from Cheniella touranensis and their cytotoxic potential in vitro - Xing-Ping Zhang; Yun Wang; Jia-Le Wang; Wu-Yan Chen; Wen-Jie Ma; Yan-Heng Zhou; Ming-Ming Li; Kou Wang (Phytochemistry, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Trace element sources, migration and health risks associated with river-groundwater interaction: Insights from isotopes, fluorescence spectroscopy and Monte Carlo simulation - Xu Yang; Muhan Li; Yiying Miao; Fuyang Huang; Zeyuan Liu; Hongli Ma; Ping Miao; Jigang Shi; Zengbao Zhang; Shen Qu; Ruihong Yu (Journal of Hydrology, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Volatile organic compounds, nutritional content, and antioxidant activities of morel mushrooms: Effects of different cooking treatments - Fuyan Li; Qian Zhang; Yufeng Qin; Yongyu Guo; Ping Shao; Lei Guo; Qian Ma; Fangyu Fan (International Journal of Gastronomy and Food Science, 2026)

Deep mantle reservoirs of recycled surface carbonates revealed by Mg-Sr-Nd-Pb isotopes in continental basalts - Yan-Qing Li; Chang-Qian Ma; Xiao-Ping Xia; Bin Liu; Ji-Ping Yu; Xiang-Yun Hu (Geochimica et Cosmochimica Acta, 2026)

Integrating water use efficiency dynamics into ecological function zoning: Patterns, drivers, and trade-offs - Libin Zhang; Jiaxing Zhang; Qiang Ma; Jianzhu Li; Keke Zhou; Ting Zhang; Ping Feng (Environmental Research, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Multi-omics integrated analysis reveals the key metabolic regulation mechanisms of petal color in Phalaenopsis aphrodite Rchb.f - Yuqing Sun; Na Meng; Ping Li; Tingting Ren; Chunyan Dong; Chunling Wang; Siqi Ma; Yiqiang Li (Plant Cell Reports, 2026)

Effects of fish meal replacement with bullfrog skin meal on growth performance, muscle quality, and hepatointestinal health in grass carp, Ctenopharyngodon idella - Jingjing Tian; Yongjie Ma; Ping Wang; Mengmeng Ji; Yun Xia; Kai Zhang; Hongyan Li; Wangbao Gong; Zhifei Li; Wenping Xie; Quanfa Zhong; Guangjun Wang; et al. (Animal Feed Science and Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

Irrigation enhanced nitrification and hydrological partitioning drive groundwater nitrate accumulation in an agricultural irrigation district - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Shen Qu; Dong Qian; Muhan Li; Zeyuan Liu; Ping Miao; Hongli Ma (Journal of Hydrology, 2026)

Changes in perceptions of cultural ecosystem services in urban coastal park during different phases of COVID-19: Integrating the prompt engineering and aspect-based sentiment analysis with a large language model - Zirui Zhao; Ping Li; Bin Chen; Weiwei Yu; Wenjia Hu; Zhiyuan Ma; Jianji Liao (Journal of Cleaner Production, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Regulating interfacial electronic structure in Fe2O3/g-C3N4 heterogeneous fenton catalyst for efficient low-temperature flue gas denitrification - Huidong Tang; Chen Liu; Donggou Sun; Wenbo Zhang; Xiaohua Zhu; Yixing Ma; Jiacheng Bao; Kai Li; Xin Sun; Ping Ning (Chemical Engineering Journal, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Direct quantification of thallium(I) in water by ESI-MS via supramolecular recognition with cryptand[2.2.2] - Hai Li; Ping Guo; Min Li; Ming Ma; Wei Luo; Bo Chen (Analytica Chimica Acta, 2026)

Integrating Clinical Evidence with PBPK Modeling to Assess PPI-Clopidogrel-CYP2C19 Interactions in Chinese ACS Patients - Ya-xin Liu; Yun Kuang; Jun-long Ma; Jin-long Liu; Nuo Xu; Qi Pei; Li-ying Gong; Guo-ping Yang (Pharmaceutical Research, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Biochar and zero-valent iron synergistically enhance high-strength food wastewater treatment in an anaerobic baffled reactor: Optimization of functional compartmentalization and stability mechanisms - Fanfan Ma; Cong Jin; Ziqin Zhang; Jinhua Wu; Ping Li (Journal of Water Process Engineering, 2026)

Preparation of negative carbon cement soil by corn straw biochar collaborative carbonization technology: Mechanical properties, carbon sequestration evaluation, microscopic mechanism - Pengfei Wei; Wei Wang; Xukun Ma; Na Li; Chenjun Wang; Yong Liu; Ping Jiang; Miaomiao Sun (Journal of Environmental Management, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Recent advances in spectroscopic techniques for detecting foodborne pathogens in milk: A review - Ping An; Tingting Li; Haonan Yu; Xinyi Liu; Haiyan Ma; Ning Ju; Zhongxiong Zhang; Songlei Wang (International Dairy Journal, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Paleoclimatic evolution of the northeastern Tibetan Plateau margin during the Late Oligocene-Early Miocene: Evidence from Ostracod shell trace elements - Wei Chen; Jinlong Ma; Xiaofeng Wang; Xuan Li; Liang Zeng; Xiaoqing Jiang; Ping Yang; Houyong Luo; Ke Yin (Journal of Mountain Science, 2026)

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Avermectin disrupts blood-brain barrier integrity in zebrafish larvae via the Wnt/β-catenin signaling pathway - Wei-Guo Wang; Lin-Jing Du; Huan-Ou Ma; Wen-Ping Xu; Li-Ming Tao; Zhong Li; Jia-Gao Cheng; Li Zhao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

SOC1 clade genes coordinate lateral root development and response to multiple phytohormonal and environmental stress signals in Arabidopsis - Xinyue Li; Qian Ma; Ping Jin; Yaxuan Wang; Tongyao Yang; Ying Chen; Shujuan Guo; Zisheng Zhang; Chengbin Xiang; Qiuling Wang; Linhui Yu (Journal of Plant Physiology, 2026)

Strategic ultrasonic regulation of Saccharomyces cerevisiae fermentation for enhanced anthocyanin production and wine quality - Jiaqi Wang; Jianing Li; Jiming Li; Ping Wang; Guoli Cheng; Binsheng Wei; Tingting Ma; Yulin Fang; Xiangyu Sun (Food Research International, 2026)

Functional characterization of fungal laccases via siRNA silencing enables targeted biodegradation - Jiaqi Sun; Lianyan Yuan; Mengna Niu; Ping Xu; Jinsheng Lin; Cuixin Li; Lin Ma; Huiping Li; Qiang Wang; Shaoxuan Qu (Environmental Pollution, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Insights into the size effect of Fe3O4 in Fe/AC for Hg0 removal and the corresponding mechanism - Jiawen Tan; Yuan Qin; Jiayi Piao; Zhao Li; Fei Wang; Ping Ning; Kai Li; Yixing Ma; Xin Sun (ENGINEERING Environment, 2026)

Isolation and whole-genome sequencing of antibiotic-resistant bacteria revealed the reservoir for indigenous antibiotic resistance genes in the deepest ocean sediment of the Challenger Deep - Wenmian Ding; Yuepeng Wang; Yuewei Ma; Ping Chen; Ji Yang; Zhiping Song; Yuguo Wang; Wenju Zhang; Xuan Li; Yanyan Huang; Peng Nan (Marine Pollution Bulletin, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Synergistic effects of dual enzymatic hydrolysis and heat-moisture treatment on starch digestibility and structure in multi-grain flour - Xinrui Ren; Pai Peng; Qianying Ma; Xiaolong Wang; Ping Li; Xinzhong Hu (Food Research International, 2026)

Ultra-sensitive and highly stable position-pressure dual-modal flexible sensor for human-computer interaction - Jiufei Luo; Xuejun Ma; Xiaolin Zheng; Yuxin Li; Zhidan Luo; Yi Lu; Ping-an Yang (Chemical Engineering Journal, 2026)

Impacts of diverse urbanization scenarios on typhoon precipitation patterns in the Pearl River Delta: A case study of Typhoon Mangkhut - Yongwei He; Zhongming Gao; Yulong Ma; Ping Zhou; Jingyu Yao; Xixi Yang; Lei Li (Atmospheric Research, 2026)

Long-term organic amendments accelerate straw decomposition via specialized microbial enrichment in greenhouse vegetable soils - Long Ma; Shaowen Huang; Dali Song; Chao Ai; Ruonan Li; Liying Wang; Ping He; Wei Zhou (Applied Soil Ecology, 2026)

Dynamic response of an FPSO flare tower with tubular joints under combined wind-wave loads - Qian Li; Huan Ping; Jiamin Guo; Fengxi Song; Weize Ma (Ocean Engineering, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Efficient depolymerization of polystyrene waste into styrene monomers over the microwave-assisted Zn/b-ZnO catalyst system - Zijian Zhang; Bonan Liu; Li Yang; Jingwen Wang; Yuqing Dong; Chao Tang; Ping Wang; Haijiao Xie; Lei Zhang; Lu Zhang; Jun Zhao; Yu Fan; et al. (Journal of Environmental Chemical Engineering, 2026)

Metal mixture exposure and elevated risk of hypertensive disorders in pregnancy: Insights from a case-control study in northwestern China - Xueman Ding; Li Liu; Zhaochun Liu; Shurui Zuo; Yu Huang; Yizhong Yan; Shangzhi Xu; Ping Yao; Menghuan Xiao; Chengxian Dong; Chulin Yan; Xiaoyu Song; et al. (Journal of Environmental Sciences, 2026)

In-situ tar reduction and catalytic reforming in sewage sludge gasification using steel slag oxygen carrier - Quxiu Dai; Qianrong Zhang; Nanqi Ren; Jiawei Li; Qihong Cen; Wang Du; Longgui Xie; Liping Ma; Ping Ning; Binbin He (Bioresource Technology, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Clonal hematopoiesis mutation is associated with risk of incident lung cancer and death - Ying Zhu; Chen Zhu; Ping Li; Ruiqi Ma; Dan Zhou; Kai Li; Jianzheng Zhang; Qiang Tong (GeroScience, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Understanding public perceptions of cultural ecosystem services in urban coastal wetland ecological restoration areas: A social media-based large language model approach - Zirui Zhao; Zhiyuan Ma; Bin Chen; Ping Li; Weiwei Yu; Wenjia Hu; Dian Zhang; Jianji Liao (Journal of Environmental Management, 2026)

Corrigendum to “Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease” [Chem. Eng. J. 464 (2023) 142690] - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping’an Ma; et al. (Chemical Engineering Journal, 2026)

Co-assembly of natural small molecules from Cordyceps militaris into a carrier-free hydrogel targeting Egr1-CSPG4-AKT signaling for glioblastoma therapy - Yong Hou; Lei Chen; Zongyang Li; Xiangbao Meng; Yuecheng Liu; Fanfan Chen; Weiping Li; Jihu Yang; Xudong Xu; Ping Cui; Guoxu Ma; Guodong Huang (Chemical Engineering Journal, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Nitrogen conversion and Feammox potential driven by microorganisms around the iron ore tailings pond - Yifan Jiang; Zhengbo Yue; Jin Wang; Ziyi Li; Xin Pan; Qinglong Guo; Zhiguo Li; Ping Guo; Ding Ma (Environment, Development and Sustainability, 2026)

UVB-activated permanganate enables rapid emerging organic contaminants decontamination through synergistic HO• and reactive manganese species - Ping Li; Peng Su; Qixiao Lv; Qiuling Lu; Ying Xu; Xiangyang Hou; Jucai Xu; Jun Ma; Tao Yang (Water Research, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Dermal exposure to heavy metals contaminated soil from e-waste sites: Linking bioaccessibility to cellular uptake, cytotoxicity, and transport mechanisms in skin cells - Daolei Cui; Hua Zhong; Ziya Ma; Yiping Cheng; Chengxin Liu; Jingya Li; Jiaoyang Ma; Ping Xiang (Journal of Hazardous Materials, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Mechanistic investigations into cytochrome c-U(VI) adsorption-reduction on ferrihydrite: Implications for subsurface microbial U redox under anaerobic conditions - Jiayu Song; Huiyang Mei; Xiangxian Ma; Ghufran Uddin; Jianjun Liang; Ping Li; Weichao Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Polyetheramine-derived hydrophobic di-cationic ionic liquids for moisture tolerant and selective SF₆ recovery - Yi Pan; Fengyu Fu; Yu Dou; Bin He; Zhiyan Ma; Panpan Mi; Ping He; Wei Kou; Changli Li; Lixin Xia (Journal of Environmental Chemical Engineering, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Lactic acid bacteria in Jiangxiangxing Baijiu fermentation: Resource exploration, community succession and their ecological dynamics - Pan Huang; Zhongfu Duan; Shiyuan Ma; Wei Cheng; Qiuxia Li; Dan Huang; Ping Huang; Rongqing Zhou; Jiao Niu; Yadong Zhang; Chongde Wu (Food Bioscience, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Measuring grazing grassland aboveground biomass and spatial heterogeneity based on UAV LiDAR observation with upscaling samples - Yu-Qing Wu; Li-Biao Guo; Wei-Xian Tan; Ping-Ping Huang; Ming-Ze Ma; Yang Zhao (International Journal of Remote Sensing, 2026)

Impacts of acidification and warming on carbon sequestration capacity in Pacific oysters: Roles of biosynthesis and biodeposition - Zi-Jing Meng; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Ping Li; Zhi-Hua Li (Aquaculture, 2026)

Late Cretaceous intracontinental subduction along the Bangong-Nujiang Suture Zone: evidence from the K-rich magmatism in the Lunpola Basin, central Tibetan Plateau - Ping Wang; Haijian Lu; Liang Duan; Xuxuan Ma; Yihu Zhang; Wang Li (Tectonophysics, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Long-term chemical fertilizer application enhances ammonia oxidizers-mediated soil carbon neutrality - Xueru Huang; Zhuo Zhang; Taoyi Ren; Song Li; Ping Zhu; Jingjing Ma; Zhongjun Jia; Jingkuan Wang; Marcela Hernández (Soil Biology and Biochemistry, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Responses of mesozooplankton to extreme positive Indian Ocean Dipole (pIOD) and cold-core eddy in the eastern Equatorial Indian Ocean and southern Bay of Bengal during 2019/2020 winter - Ping Du; Xiao Ma; Yuanli Zhu; Ruijie Ye; Shenran Zhang; WNC Priyadarshani; P.A.K.N. Dissanayake; Haifeng Zhang; Yibo Liao; Yanbin Tang; Zhibing Jiang; Hongliang Li; et al. (Progress in Oceanography, 2026)

Pinoresinol diglucoside alleviates hindlimb unloading-induced bone loss in mice - Ying-Ying Xuan; Liang Li; Yi Wu; Zhen-Long Wei; Mei Zhang; Min-Na Liu; Dong-Shuai Shen; Yu-Hai Gao; Cory J Xian; Hui-Ping Ma; Ke-Ming Chen (Life Sciences in Space Research, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Iron-ceramsite with balanced electron transfer capacity enables simultaneous removal of refractory organics and nitrogen in coking wastewater by single-stage BAF - Hui Zhai; Ding Ma; Jin Wang; Wusong Xu; Yifan Jiang; Bixuan Sheng; Qinglong Guo; Zhiguo Li; Ping Guo; Zhengbo Yue (Chemical Engineering Journal, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Development of an integrated searching system for rapid and accurate classification of edible oils by matrix-assisted laser desorption/ionization mass spectrometry - Michael Ho-Yin Ma; Suying Li; Zhen-Yan Li; Jessie Wing-Yin Wu; Zhong-Ping Yao (Analytica Chimica Acta, 2026)

Simulating and predicting lake dynamics by fusing HBV modeling, machine learning approach and remote sensing data - Muhammad Naeem; Yongqiang Zhang; Ning Ma; Zixuan Tang; Ping Miao; Xiaoqiang Tian; Congcong Li; Qi Huang; Zhenwu Xu; Longhao wang; Zhen Huang (Journal of Hydrology, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Evaluation of carrying capacity of agricultural water and soil resources and targeted regional management in Northwest China - Yun Gao; Dawei Ding; Youming Zhang; Ping Li; Kaiyang Li; Tianhao Ruan; Yang Han; Chunya Ma (Journal of Environmental Management, 2025)

Upcycling nitrophosphate-making slag into a novel and low-cost CaO-based sorbent for CO2 capture - Ping Wang; Xiaotong Ma; Jun Li; Dongyang Weng; Xiao Lu (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

“Pit-type Defects” strategy to improve the thermal stability of silver-based catalysts and copper-based catalysts - Yatong Pang; Chunxue Wang; Ziruo Zeng; Kai Li; Yixing Ma; Yuan Li; Fei Wang; Ping Ning (Journal of Environmental Sciences, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Synergistic effects of FeCl₃-derived deoxygenation and pore formation on TiFe hydrogen storage alloys - He Zhang; Yong Liu; Guodong Miao; Zhihui Ma; Feng Sun; Aimin Ju; Xuanhui Qu; Ping Li (Chemical Engineering Journal, 2025)

Synergistic integration of tetraphenylethylene π-bridge and localized asymmetric electron distribution for enhanced photocatalytic indole C-3 thiocyanation - Baiwei Ma; Xuanyu Lin; Wenxin Liu; Pengjing Chen; Yanjie Wang; Ping Li; Xiaobin Lin; Lipeng Zhai; Mengyang Li (Chemical Engineering Journal, 2025)

Phosphorus incorporation drives charge distribution optimization and oxygen deficiency of cobalt‑nickel oxide nanoflakes with enhanced electrochemical performance for supercapacitor - Qinghai Ma; Ping Wang; Gaofeng Li; Fang Cui; Bin Yang; Zhijun Qiao; Dianbo Ruan; Xing Liu; Tieyu Cui (Chemical Engineering Journal, 2025)

Conservation prioritization based on plant richness and endemism in Myanmar - Thant Sin Aung; Xiao-Li Shen; Alice C. Hughes; Ke-Ping Ma (Biological Conservation, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Predictive value of serum lipid for kawasaki disease shock syndrome: a prospective study - Ping Wu; Bowen Li; Jinlin Wu; Yunhao Li; Fan Ma; Nanjun Zhang; Xiaoliang Liu; Yimin Hua; Kaiyu Zhou; Chuan Wang; Hongyu Duan; Shuran Shao (Immunologic Research, 2025)

Discovering novel type I collagen fragments from Cyprinus carpio supporting bone regeneration - Jianhua Zeng; Miao Chen; Xinglong Wang; Huan Yu; Liang Zhang; Yongxing Peng; Ping Wan; Zhongshi Huang; Fuqiang Ma; Jingtang Li (Functional & Integrative Genomics, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Exposure to high air humidity and Aspergillus niger (aerosol) environments exacerbates asthma inflammation and metabolite dysfunction in mice through the TRPA1 and TRPV4 neural pathways - Chenqiu Du; Meixing Wu; Xu Yang; Baizhan Li; Yang Wu; Gen Li; Ping Ma (Journal of Hazardous Materials, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Piezoelectric polarization-induced electric field in Co-Co2P/BNT composite for enhanced peroxymonosulfate activation and rapid degradation of sulfamethoxazole - Xunwu Yang; Xiaomei Ma; Haodi Yang; Jie Zhao; Yigui Tang; Ping Ning; Chi Wang; Guijian Zhang; Shuangyou Bao; Kai Li (Journal of Environmental Chemical Engineering, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

A feasible method for preparing garnet matrix with vertically aligned microchannels for all-solid-state lithium batteries - Ruotong Ma; Chi Zhang; Wenyi Xiang; Lihan Chen; Zongzi Jin; Cui Li; Lei Zhang; Weiwei Ping; Chusheng Chen; Chengwei Wang (Chemical Engineering Journal, 2025)

Economical and efficient production of l-norvaline using whole cells of Escherichia coli with an enzymatic cascade - Zimai Li; Qiaoyue Yang; Mingyuan Liu; Hairong Yu; Qihang Du; Hongxu Zhang; Jinglong Deng; Xiaoxu Tan; Weikang Sun; Tianyi Jiang; Qianjin Kang; Wensi Meng; et al. (Bioresource Technology, 2025)

Chemical constituents of Engleromyces sinensis and their chemotaxonomic significance - Xiao-Xue Jiang; Lai-Wei Li; Xing-Ping Zhang; Ke-Pu Huang; Wen-Jie Ma; Li-Ping Tang; Kou Wang (Biochemical Systematics and Ecology, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Transcriptome profiling of mRNA responding to inflammation in bovine mammary epithelial cells induced by lipopolysaccharide - Jin-peng Wang; Zheng-xing Wang; Bin-wu Bao; Yan-xia Li; Zhuo-ma Luoreng; Xing-ping Wang (Research in Veterinary Science, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Molecular mechanisms underlying multi-generational skeletal abnormalities in marine medaka induced by the quinolone antibiotic norfloxacin (NOR) - Cun-Long Wang; Ping Li; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Metabolic mechanism of a novel carboxylesterase YvaK in Priestia aryabhattai DPX-1 for carbamate insecticide indoxacarb detoxification - Ping Zou; Zijing Li; Shengyang Li; Yuehan Geng; Xin Ma; Xiangwei Wu; Rimao Hua; Liancheng Fang (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Activity and sulfur resistance enhancement of metal-based catalysts derived from layered double hydroxides for selective catalytic reduction of NO with NH3 - Gan Chen; Zhenzhen Guan; Shifeng Zhou; Yu Guo; Ziying Yang; Jiang Wu; Fangqin Li; Ping He; Xinxia Ma (Fuel, 2025)

Black tea addition enhances the aroma release of rose petals by activating related pathways during the scenting process - Yueling Zhao; Liuyi Chen; Jinlin Bian; Faxin Li; Yuanyuan Wang; Hongyu Zhou; Zihan Ma; Ping Xu; Xiao Du (Food Chemistry, 2025)

Rational screening of covalent organic frameworks for solid-phase microextraction of advanced glycation end products from thermally processed foods - Xiao-Fan Lu; Xin-Yu Li; Rongyu Wang; Wenhua Ji; Jian-Ping Ma; Dian-Shun Guo (Food Chemistry, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Long-Term Fertilization Effects on Forms and Availability of Phosphorus Associated with Humic Substance Fractions in a Mollisol in Northeast China - Jinjing Zhang; Yuanhong Sun; Yuhan Yuan; Hongbin Ma; Yanhui Feng; Zhihan Zhang; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

Investigating the Impact of Drought During Returning Green and Jointing Stages on Different Tillers Position of Winter Wheat - Muhammad Fraz Ali; Ping Li; Lijuan Ma; Changjie Feng; Shubo Gu; Xiang Lin; Dong Wang (Journal of Plant Growth Regulation, 2025)

A prospective study on the regulation of osteoarthritis risk through inflammatory pathways in clonal hematopoiesis - Ping Li; Zijian Kang; Ruiqi Ma; Chen Zhu; Ying Zhu; Iris Tang; Jianzheng Zhang; Kai Li; Qiang Tong (GeroScience, 2025)

Proteomics and metabolomics reveal the role of miR-320b in regulating inflammation of bovine mammary epithelial cells - Li Zhou; Zhuo-Ma Luoreng; Xing-Ping Wang; Ya-Qing Dou; Hui Li (Research in Veterinary Science, 2025)

Association of microplastics in human cerebrospinal fluid with Alzheimer’s disease-related changes - Ping He; Feng Wang; Guangjun Xi; Yang Li; Fengyun Wang; Hui Wang; Lei Li; Xuemei Ma; Yan Han; Yachen Shi (Journal of Hazardous Materials, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Identifying the determinants of natural, anthropogenic factors and precursors on PM1 pollution in urban agglomerations in China: Insights from optimal parameter-based geographic detector and robust geographic weighted regression models - Ping Zhang; Yong Wang; Wenjie Ma; Mingyao Li; Yonghua Zhao; Wentao Wang; Yefan Jia; Jinghao Fan; Lufang Kong; Kang Hou; Yuanyuan Han (Environmental Research, 2025)

Bioluminescent fungi-inspired room temperature phosphorescence mycelia - Xin Li; Jin-Xin Ma; Ping Wu; Qian Gao; Hao Wang; Lu-Xin Tang; Feng Peng; Bao-Zhong Lü; Jing Si; Bao-Kai Cui (Chemical Engineering Journal, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Mineralized degradation of bisphenol A by novel photoenzyme-metal catalyst FCAP@Ag3PO4/Lac-Pd beads - Linmeng Ma; Ping Xue; Zhiguo Gao; Chongrui Xu; Peng Li (Journal of Environmental Management, 2025)

Microwave-induced strength reduction and weakening mechanisms of basic rocks - Zhongjun Ma; Xiaobao Zhao; Han Li; Hanwen Liu; Yangwei Long; Yanlong Zheng; Ping Che (International Journal of Rock Mechanics and Mining Sciences, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Study on the high-efficiency CO2 mineralization reaction mechanism of thermally modified materials from neutralized gypsum residue driven by sulfur vacancies in an aqueous environment - Yuwen Deng; Sisi Chen; Huidong Tang; Fei Wang; Yixing Ma; Lei Shi; Fan Du; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Research Progress on Grapevine Response Mechanisms and Alleviation Measures Under Salt Stress - Ying Lai; Congcong Zhang; Haokai Yan; Guojie Nai; Jinyu Bao; Ping Sun; Yuan Liu; Jingrong Zhang; Zhihui Pu; Sheng Li; Shaoying Ma (Journal of Plant Growth Regulation, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Fate of polystyrene micro- and nanoplastics in zebrafish liver cells: Influence of protein corona on transport, oxidative stress, and glycolipid metabolism - Ling Liu; Yanan Xu; Yuqing Ma; Fengshang Duan; Cunlong Wang; Jianxue Feng; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Recognizing the state of aerobic granular sludge over its life-cycle in a continuous-flow membrane bioreactor with an artificial intelligence approach - Yu Zeng; Chenguang Zhao; Danling Ma; Liying Bin; Weirui Chen; Ping Li; Bing Tang (Journal of Environmental Management, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Transgenerational thyroid hormone disruption in zebrafish induced by environmentally relevant concentrations of triclosan - Ping Ding; Jiayi Zhang; Xin Li; Pengcheng Ma; Guocheng Hu; Lijuan Zhang; Yunjiang Yu (Environmental Pollution, 2025)

An enzyme-activated fluorescent probe for proline aminopeptidase and its applications in anti-infection agent discovery - Ming Zhang; Lei Feng; Shengui He; Chaoyan Han; Yuzhuo Wu; Jingnan Cui; Ping Guo; Dawei Li; Chao Wang; Xiaochi Ma (Chemical Engineering Journal, 2025)

Insights into mantle metasomatism during oceanic subduction from late Paleozoic (∼260 Ma) high-Mg diorites in the northeastern Tibetan Plateau - Feng-Hui Zou; Jian-Ping Zheng; Cai-Lai Wu; Chang-Qian Ma; Li-Huan Deng (Chemical Geology, 2025)

The molecular mechanism by which CTSB degrades FPN to disrupt macrophage iron homeostasis and promote the progression of atherosclerosis - Quanli Qiu; Qiyu Sun; Jiaxin Yang; Qingxin Yuan; Ping Wang; Qingwei Liu; Zhenzhen Cui; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2025)

A safety and absolute activity measurement method for Phi29 DNA polymerase based on chemiluminescent detection of dATP consumption - Xuefeng Wang; Ping Gui; Xiao Li; Feng Lu; Wei Jing; Changlong Li; Zelin Lu; Yanna Lin; Huancai Yin; Haichao Li; Fuqiang Ma (Analytica Chimica Acta, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Preparation of half-coated manganese oxide lithium ion-sieve precursor with low manganese dissolution loss for lithium recovery - Ping Liu; Xiaolong Yan; Zhen Chen; Yuanhang Qin; Li Yang; Jiayu Ma (Journal of Water Process Engineering, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Effect of Cu/HZSM-5 sorbents with different Si/Al ratios on the adsorption and oxidation performance of H2S - Kaini Ma; Kai Li; Ping Ning; Jiayu Feng; Jiacheng Bao; Lei Shi; Xiangyu Wang; Xin Sun (Journal of Environmental Sciences, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Piezoelectric-enhanced rapid degradation of sulfamethoxazole using the Co3O4/Bi0.5Na0.5TiO3/Peroxymonosulfate process - Xiaomei Ma; Xunwu Yang; Kai Li; Ping Ning; Xin Sun; Yigui Tang; Shuangyou Bao; Chi Wang (Chemical Engineering Journal, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Hydrochemical insights into spatiotemporal characteristics of groundwater salinization and health risk assessment of fluoride in the south bank of Yellow River irrigation area, Northwest China - Muhan Li; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Rina Wu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Environmental Geochemistry and Health, 2025)

Intravenous immunoglobulin ameliorates doxorubicin-induced intestinal mucositis by inhibiting the Syk/PI3K/Akt axis and ferroptosis - Xiaochen Yan; Peng Jiang; Changqing Li; Fengjuan Liu; Ping Fu; Dengqun Liu; Xi Du; Li Ma; Tong Wang; Xin Yuan; Shengliang Ye; Zongkui Wang (Apoptosis, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

A method for the identification and evaluation of Glycyrrhiza germplasm based on DNA barcodes and leaf micromorphology - Zhenzhu Du; Wenbin Xu; Yuxia Wang; Zhancang Ma; Ping Yan; Gang Huang; Hongbin Li (Flora, 2025)

Integrating three-primary-color and white long-lasting afterglows in triphenylene-doped polymers for time/space-resolved applications - Qian Wang; Xiao-Lei Xu; Meng-Yuan Zhu; Ya-Ping Du; Yu-Juan Ma; Jin-Hua Li; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Underlying the early signaling and gene expression of Pleurotus ostreatus mycelia during injury response - Jiachun Zhu; Jiaqi Sun; Huiping Li; Ping Xu; Lin Ma; Qiang Wang; Keping Chen; Shaoxuan Qu (World Journal of Microbiology and Biotechnology, 2025)

ADAR1 Promotes NUPR1 A-to-I RNA Editing to Exacerbate Ischemic Brain Injury by Microglia Mediated Neuroinflammation - Guo-Ping Wang; Wen-Juan Li; Ye Li; Ming-Xing Ma; Kai-Kai Guo (NeuroMolecular Medicine, 2025)

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The catalytic mechanism of cobalt-based sites in the oxidation of MgSO3 - Zhaorui Li; Xin Tang; Fei Wang; Kai Li; Shi Lei; Ning Ping; XingYi Ma; Xin Sun (Process Safety and Environmental Protection, 2025)

Liubao tea extract restrains obesity-related hyperlipidemia via regulation of AMPK/p38/NF-κB pathway and intestinal microbiota - Xinyu Feng; Yuechao Qin; Shicheng Ma; Shengjin Ming; Zhihang Weng; Yuqi Xuan; Shuying Gong; Fangyuan Fan; Ping Chen; Qiang Chu; Zhongxia Li (Food Chemistry, 2025)

Regulation of multilayer long crystalline MoS2 by NiO-modified Al2O3 for improved hydrodesulfurization of COS - Yubiao Li; Yu Liu; Xueqian Wang; Yixing Ma; Ping Ning; Langlang Wang; Xiang Li; Rui Cao (Environmental Research, 2025)

Biotransport and toxic effects of micro- and nanoplastics in fish model and their potential risk to humans: A review - Yanan Xu; Ling Liu; Yuqing Ma; Cunlong Wang; Fengshang Duan; Jianxue Feng; Haiyang Yin; Le Sun; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Aquatic Toxicology, 2025)

Stochastic hazard assessment framework of landslide blocking river by depth-integrated continuum method and random field theory - Shui-Hua Jiang; Jian-Ping Li; Guotao Ma; Mohammad Rezania; Jinsong Huang (Landslides, 2025)
Landslide-induced barrier dams pose a threat to the safety of humans, livestock and nearby infrastructures. The efficient assessment of landslide blocking river is crucial for disaster prevention and mitigation solutions. This study proposes a novel stochastic assessment framework to evaluate the landslide blocking river through the prediction of their deposition depths and considering the heterogeneity of shear strength parameters on the potential sliding surface. The depth-integrated continuum method (DICM) is used to simulate the landslide runout process. Using an enhanced Karhunen-Loève expansion (KLE) method, the spatial variations in soil's shear strength parameters are modeled by random fields to incorporate the effects of soil's spatial heterogeneity on the landslide deposition pattern. Subsequently, the multi-response surrogate model is constructed to relate the random field variables to the deposition depths based on extreme gradient boosting (XGBoost). To improve the performance of the surrogate model, principal component analysis (PCA) and sliced inverse regression (SIR) methods are employed for the dimension reduction of output and input variables, respectively. Furthermore, the algorithm for river blockage identification is developed to search for the deposition ridges. To demonstrate the capability of the stochastic assessment framework, an example of the first Baige landslide in Tibet, China is simulated, and the affected region and deposition depths of the landslide are predicted to calculate the probability of river damming. The presented methodology provides a practical means for improving the landslide blocking river prediction and new insights for early warning and risk mitigation.

Evaluation of Potentially Toxic Metal Bioaccumulation in Farmed Mussels: Assessing the Non-Contributory Role of Attachment Ropes in Metal Enrichment - Wei Ma; Xuelian Wei; Fenglian Zeng; Ming Li; Ping Wang; Jiji Li (Bulletin of Environmental Contamination and Toxicology, 2025)

Influence of topography on the fragmentation and mobility of landslides - Zhaodong Li; Jian Guo; Tonglu Li; Ping Li; Xuetong Ma; Mengmeng Zhang; Enxian Jia; Pingping Xu (Bulletin of Engineering Geology and the Environment, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Probabilistic evaluation of landslide influence zones considering stratigraphic dips and nonstationarity of soil properties - Jian-Ping Li; Shui-Hua Jiang; Guo-Tao Ma; Mohammad Rezania; Mohaddeseh Mousavi Nezhad; Jian-Hong Wan (Computers and Geotechnics, 2025)

Dominant spring precipitation anomaly modes and circulation characteristics in the Tarim Basin, Central Asia - Dilinuer Tuoliewubieke; Junqiang Yao; Weiyi Mao; Ping Chen; Liyun Ma; Jing Chen; Shujuan Li (Atmospheric Research, 2025)

Transcriptome and metabolism study reveals impact of nitrogen fertilizer on triticale - Xiaojuan Zhang; Hongxiu Ma; Peng Jiang; Yongwei Chen; Wenli Ma; Ping Chen; Hongcai Ma; Xuexue Li; Jiale Ma; Quan Sun (Protoplasma, 2025)

Di-(2-ethylhexyl) Phthalate Exposure Induces Developmental Toxicity in the Mouse Fetal Heart via Mitochondrial Dysfunction - Yafei Guo; Bowen Li; Yu Yan; Nanjun Zhang; Shuran Shao; Lixia Yang; Lixue Ouyang; Ping Wu; Fan Ma; Hongyu Duan; Kaiyu Zhou; Yimin Hua; et al. (Cardiovascular Toxicology, 2025)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Potential ecological risk assessment for trace metal(loid)s in soil surrounding coal gangue heaps based on source-oriented - Jie Ma; Zhijie Shen; Yue Jiang; Ping Liu; Jing Sun; Mingsheng Li; Xue Feng (Science of The Total Environment, 2024)

Melatonin protects spermatogenic cells against DNA damage and necroptosis induced by atrazine - Tian-Ning Yang; Ning-Ning Huang; Yu-Xiang Wang; Ping-An Jian; Xiang-Yu Ma; Xue-Nan Li; Jin-Long Li (Pesticide Biochemistry and Physiology, 2024)

Corrigendum to “Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism” [J Hazard Mater Vol 480, 2024, 136236] - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhihua Li (Journal of Hazardous Materials, 2024)

Multigenerational effects of combined exposure of triphenyltin and micro/nanoplastics on marine medaka (Oryzias melastigma): From molecular levels to behavioral response - Jian-Xue Feng; Bin Liu; Cheng-Zhuang Chen; Yu-Qing Ma; Cun-Long Wang; Ya-Nan Xu; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Mechanisms of eco-corona effects on micro(nano)plastics in marine medaka: Insights into translocation, immunity, and energy metabolism - Ling Liu; Yuqing Ma; Yanan Xu; Bin Liu; Cunlong Wang; Jianxue Feng; Mingyang Li; Haiyang Yin; Le Sun; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2024)

Environmental behavior and toxic effects of micro(nano)plastics and engineered nanoparticles on marine organisms under ocean acidification: A review - Ling Liu; Haiyang Yin; Yanan Xu; Bin Liu; Yuqing Ma; Jianxue Feng; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Environmental Research, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Effects of nanoplastics on the growth, transcription, and metabolism of rice (Oryza sativa L.) and synergistic effects in the presence of iron plaque and humic acid - Xiaoxue Ouyang; Jie Ma; Bingcong Feng; Yong Liu; Ping Yin; Xiaoyu Zhang; Pan Li; Qiusheng Chen; Yujie Zhao; Liping Weng; Yongtao Li (Environmental Pollution, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

8-Br-cGMP suppresses tumor progression through EGFR/PLC γ1 pathway in epithelial ovarian cancer - Min Wu; Chunyan Mu; Huiwen Yang; Yue Wang; Ping Ma; Shibao Li; Zhongcheng Wang; Ting Lan (Molecular Biology Reports, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

Comprehensive determination of fatty acids in real samples without derivatization by DMU-SPME-GC methods - Yun-Jiao Ma; Ping Li; Bei-Wei Zhu; Ming Du; Xian-Bing Xu (Food Research International, 2024)

Phase change-mediated core-sheath 3D printing of hollow microlattice pseudocapacitive aerogel electrode with favorable electrochemical properties - Chunjing Zhang; Chenyang Song; Yuyan Ma; Li Chen; Yutao Niu; Liming Zhao; Ping Li; Yongyi Zhang; Zhengpeng Yang (Chemical Engineering Journal, 2024)

Holocene aeolian environmental dynamics in fixed and semi-fixed deserts over the arid Central Asia revealed by comprehensive sand-dune records - Min Cao; Ping Lü; Fang Ma; Linhai Yang; Junlin Yu; Zishu Xia; Chao Li (CATENA, 2024)

Effects of microplastics on potato verticillium wilt and microbial community of rhizosphere soil - Naqi Cui; Hongwu Liang; Weisong Zhao; Mingzhu Zhao; Yu Wang; Qinggang Guo; Zihui Rong; Shezeng Li; Ping Ma (Applied Soil Ecology, 2024)

Responses of soil microbial community diversity and co-occurrence networks to interspecific interactions in soybean/maize and peanut/maize intercropping systems - Huai-Ying Ma; Surigaoge Surigaoge; Yi Xu; Yu-Chen Li; Peter Christie; Wei Ping Zhang; Long Li (Applied Soil Ecology, 2024)

Mechanisms of exacerbation of Th2-mediated eosinophilic allergic asthma induced by plastic pollution derivatives (PPD): A molecular toxicological study involving lung cell ferroptosis and metabolomics - Huaqin Wei; Surui Lu; Mingqing Chen; Runming Yao; Biao Yan; Qing Li; Xiaoli Song; Mengcheng Li; Yang Wu; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Activation mechanism of CoFe2O4 nanocatalysts on different oxidants and degradation efficiency of butyl xanthate - Xiaoqi Wu; Zhaoyang Song; Qiongqiong He; Yifei Li; Pengxu Xiang; Yuan Xu; Ping Ma (Minerals Engineering, 2024)

Reduction and immobilization of Cr(VI)-contaminated soil using FeSO4 combined with (NH4)2HPO4: The remediation efficiency, mechanisms, and long-term stability - Jiachao Jiang; Haibo Chen; Qunqun Li; Xu Xia; Jianli Ma; Lizhang Wang; Ping Luo (Journal of Environmental Chemical Engineering, 2024)

Controlled dispersion and morphology in MoS2/SBA-15 catalysts for enhanced COS hydrodesulfurization - Li Yubiao; Cao Rui; Liu Yu; Wang Langlang; Ning Ping; Wang Xueqian; Ma Yixing (Fuel, 2024)

Effect of turbulent mixing on the formation of intermediate nepheloid layer over the northern continental slope of the Andaman sea - Ruijie Ye; Feng Zhou; Xiao Ma; Chenggang Liu; Qicheng Meng; Di Tian; Ruoyu Guo; Hongliang Li; Lu Shou; Ping Du; Soe Moe Lwin (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Efficient continuous synthesis of long-chain alkylbenzenes catalyzed by ionic liquids in microreaction systems - Haoran Ma; Wei Zhao; Ping Li; Ailing Huang (Chemical Engineering Journal, 2024)

Manganese mineralization constrained by redox conditions in the Cryogenian Nanhua Basin, South China and its implications for nitrogen and carbon cycling - Ping Wang; Jian Wang; Yuansheng Du; Wenchao Yu; Qi Zhou; Li Tian; Liangjun Yuan; Wen Pan; Wei Wei; Yongjun Qin; Zhixin Ma (Frontiers in Marine Science, 2024)
The Nanhua Basin of South China recorded complete Cryogenian stratigraphic sequence from the Sturtian Glaciation (~717–660 Ma) to the Marinoan Glaciation (~654–635 Ma). The interglacial Datangpo Fm in the Nanhua Basin is divided into two members, and the first member consists of the Mn-carbonate unit and the overlying black shale unit, containing a series of large and superlarge manganese deposits. The metallogenic process of manganese deposits is not clear, and the Mn-carbonates formed through the precursor of Mn-oxide/oxyhydroxide reduction or directly precipitated from an anoxic water column. Moreover, the redox conditions in the deep Nanhua Basin during the precipitation of manganese deposits are also controversial. In this study, the high-resolution nitrogen contents (TN), isotope compositions, carbon isotope compositions of organic and inorganic matter from the first member of the Datangpo Fm are analyzed. The δ 15 N values of the Mn-carbonate unit (+1.53‰ to +5.26‰, mean +3.36‰) are higher than those of the overlying black shale unit (−3.74‰ to +3.54‰, mean +0.89‰). The Mn contents show a negative relationship with TN but a positive relationship with δ 15 N in the Mn-carbonate unit, implying that the formation of Mn-carbonates is related to redox variations. The relatively higher δ 15 N values in the Mn-carbonate unit indicated oxic conditions, and NH 4 + can be released and partially oxidized during the mineralization of organic matter, resulting in the residual 15 N-enriched NH 4 + being transferred into clay minerals. Meanwhile, the lower δ 15 N values in the black shale unit indicated anoxic conditions, which recorded primary N isotope signals. The Mn-carbonate unit is characterized by negative δ 13 C carb values (−11.17‰ to −5.22‰, mean −8.30‰), which show a positive relationship with δ 13 C org , but a negative relationship with Mn contents, implying that the negative δ 13 C carb excursions were related to the organic matter degradation during Mn-carbonate formation. The findings of this study indicated that the metallogenesis of manganese deposits in the Cryogenian Nanhua Basin was constrained mainly by the oxic interval in the deep basin. The nitrogen and carbon cycling process can provide new insights into geochemical cycling after the Sturtian Glaciation.

Neurobehavioral toxicity induced by combined exposure of micro/nanoplastics and triphenyltin in marine medaka (Oryzias melastigma) - Peiran Lin; Ling Liu; Yuqing Ma; Renyan Du; Chuansen Yi; Ping Li; Yanan Xu; Haiyang Yin; Le Sun; Zhi-Hua Li (Environmental Pollution, 2024)

Efficient degradation of sulfadiazine by UV-triggered electron transfer on oxalic acid-functionalized corn straw biochar for activating peroxyacetic acid: Performance, mechanism, and theoretical calculation - Chenyu Zeng; Yongfei Ma; Ping Li; Xi Chen; Hongtao Liu; Zhikang Deng; Rui Mu; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Insights into dissolved organic carbon biodegradation process and influencing factors in shallow lakes in a metropolitan, China - Ping Jiang; Bingjie Ma; Maofei Ni; Danni Yuan; Siyue Li (Process Safety and Environmental Protection, 2024)

Multi-spectroscopic characterization of organic salt components in medicinal plant - Lingyu Han; Fang Ma; Ping He; Qun Zhou; Zhanping Li; Suqin Sun (Food Chemistry, 2024)

Decrypting the skeletal toxicity of vertebrates caused by environmental pollutants from an evolutionary perspective: From fish to mammals - Cun-Long Wang; Ping Li; Bin Liu; Yu-Qing Ma; Jian-Xue Feng; Ya-Nan Xu; Ling Liu; Zhi-Hua Li (Environmental Research, 2024)

Probabilistic assessment of 3D slope failures in spatially variable soils by cooperative stochastic material point method - Shui-Hua Jiang; Jian-Ping Li; Guo-Tao Ma; Mohammad Rezania (Computers and Geotechnics, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Comparison of Drought Stress Responses in Large- and Small-Rooted Rice Lines: Physiological, Anatomical, and Hormonal Changes - Yao Guo; Yunfeng Du; Xinze Niu; Yunjing Ma; Guoqing Song; Cougui Cao; Ping Li; Yinglong Chen; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Heterogeneous catalytic ozonation of ciprofloxacin in wastewater with red mud: Characterization and performance - Fuyu Huang; Huiru Ma; Zhanyao Li; Liqiang Zhang; Jun Li; Shouyan Chen; Ping Zhou; Guifang Chen (Journal of Water Process Engineering, 2024)

Disentangling streamflow impacts of check dams from vegetation changes - Jinkai Luan; Yongqiang Zhang; Xiaojie Li; Ning Ma; Shahid Naeem; Zhenwu Xu; Ping Miao; Ruidong Wang (Journal of Hydrology, 2024)

Relish-mediated C2H2 zinc finger protein IMZF restores Drosophila immune homeostasis via inhibiting the transcription of Imd/Tak1 - Hongjian Zhou; Li Liu; Yujia Pang; Yina Xu; Jing Wu; Fei Ma; Ping Jin; Xue Zhou (Insect Biochemistry and Molecular Biology, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Health risk assessment of heavy metal(loid)s in road dust via dermal exposure pathway from a low latitude plateau provincial capital city: The importance of toxicological verification - Jingya Li; Daolei Cui; Ziyue Yang; Jiaoyang Ma; Jianjun Liu; Yingxin Yu; Xianfeng Huang; Ping Xiang (Environmental Research, 2024)

Formation of secondary organic aerosols from Cl-initiated oxidation of anisole: Rapid release of ultrafine particles and organic chlorides - Fashuai Pan; Jiaoyang Ma; Qianqian Yan; Gaosheng Zhao; Bin Jia; Li Xu; Ping Cheng (Atmospheric Environment, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

Investigating the multiscale associations between urban landscape patterns and PM1 pollution in China using a new combined framework - Huimin Zhu; Ping Zhang; Ning Wang; Fengqian Zhang; Wenjie Ma; Feng Wen; Mingyao Li; Yong Wang; Xin Fan; Kang Hou; Yuanyuan Han (Journal of Cleaner Production, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Chitosan-based injectable hydrogel with multifunction for wound healing: A critical review - Aiqin Li; Bin Ma; Shiyao Hua; Rui Ping; Lu Ding; Bingren Tian; Xu Zhang (Carbohydrate Polymers, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

Severe nitrogen leaching and marked decline of nitrogen cycle-related genes during the cultivation of apple orchard on barren mountain - Yuwen Shen; Haining Chen; Haitao Lin; Ping Liu; Xiaozong Song; Yanan Ma; Mingli Li; Wensheng Gao; Lingling Song (Agriculture, Ecosystems & Environment, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

The effect of nitrogen input on N2O emission depends on precipitation in a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Shaokun Wang; Xujun Ma; Tom Misselbrook; Xiaoan Zuo (Science of The Total Environment, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Experimental investigation and numerical modeling of effect of specimen size on microwave-induced fracturing of diorite - Zhongjun Ma; Yanlong Zheng; Fuxin Rui; Gaofeng Zhao; Jianchun Li; Ping Che (Minerals Engineering, 2024)

Catalytic ozonation of ammonia nitrogen with powdered activated coke: Influence of operational parameters and surface chemistries - Guifang Chen; Huiru Ma; Fuyu Huang; Zhanyao Li; Liqiang Zhang; Jun Li; Ping Zhou; Shouyan Chen; Yongwei Li (Journal of Water Process Engineering, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Core-shell DOPO/caramel nano-polymer with desirable UV shielding and flame retardancy for polyamide 6 fabric - Wen-Jie Jin; Xian-Wei Cheng; Sheng-Nan Ma; Ling Li; Rui-Kai Wu; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Improving flood forecasts capability of Taihang Piedmont basin by optimizing WRF parameter combination and coupling with HEC-HMS - Ting Zhang; Ya Gao; Ping Yu; Jianzhu Li; Ping Feng; Huixin Ma (Theoretical and Applied Climatology, 2024)

Assessment of the combined vulnerability to droughts and heatwaves in Shandong Province in summer from 2000 to 2018 - Ping Yao; Baohuan Zhang; Ruihan Yang; Xiaonuo Ma; Xiangning Zhang; Tianxiao Wu; Baofu Li (Environmental Monitoring and Assessment, 2024)

Sesquiterpenes from Inula macrophylla and their anti-neuroinflammatory activity - Rui Ma; Bakhrom Komilov; Cheng-Bo Wang; Komila Alibekovna Eshbakova; Jun-Li Yang; Wei Ha; Yan-Ping Shi (Phytochemistry Letters, 2024)

Deep degradation of atrazine in water using co-immobilized laccase-1-hydroxybenzotriazole-Pd as composite biocatalyst - Juan Jia; Ping Xue; Lan Ma; Peng Li; Chongrui Xu (Journal of Hazardous Materials, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

Association between exposure to outdoor artificial light at night during pregnancy and glucose homeostasis: A prospective cohort study - Lei Zhang; Haixia Wang; Ping Zu; Xinyu Li; Shuangshuang Ma; Yuanyuan Zhu; Tianqin Xie; Fangbiao Tao; Dao-min Zhu; Peng Zhu (Environmental Research, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Clarifying the mechanism of apigenin against blood–brain barrier disruption in ischemic stroke using systems pharmacology - Xu Wang; ZiQiao Yu; Fuxiang Dong; Jinjian Li; Ping Niu; Qiyi Ta; JunMing Kan; Chunyu Ma; Moxuan Han; Junchao Yu; Dexi Zhao; Jinhua Li (Molecular Diversity, 2024)

Structural/surface characterization of transition metal element–doped H-ZSM-5 adsorbent for CH3SH removal: identification of active adsorption sites and deactivation mechanism - Yuxuan Xie; Xiao Peng; Xin Song; Ping Ning; Xin Sun; Yixing Ma; Chi Wang; Kai Li (Environmental Science and Pollution Research, 2024)

Response of dissolved carbon dioxide and methane concentration to warming in shallow lakes - Danni Yuan; Siyue Li; Y.Jun. Xu; Shiwang Ma; Kairui Zhang; Jingquan Le; Yang Wang; Bingjie Ma; Ping Jiang; Liuqing Zhang; Jun Xu (Water Research, 2024)

Quercetin alleviates the toxicity of difenoconazole to the respiratory system of carp by reducing ROS accumulation and maintaining mitochondrial dynamic balance - Xiaomeng Ji; Jiajia Guo; Yeyun Ma; Shuai Zhang; Zuwang Yang; Yuanyuan Li; Kaixin Ping; Yue Xin; Zibo Dong (Toxicology and Applied Pharmacology, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Determining buffering capacity of polydimethylsiloxane-based passive dosing for hydrophobic organic compounds in large-volume bioassays - Hao Hu; Ping Ma; Huizhen Li; Jing You (Science of The Total Environment, 2024)

Indole alkaloids isolated from the Nicotiana tabacum-derived Aspergillus fumigatus 0338 as potential inhibitors for tobacco powdery mildew and their mode of actions - Yue-Yu Ma; Gui Pu; Hua-Yin Liu; Sui Yao; Guang-Hui Kong; Yu-Ping Wu; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Qiu-Fen Hu; Feng-Xian Yang (Pesticide Biochemistry and Physiology, 2024)

Mediation of the JNC/ILC2 pathway in DBP-exacerbated allergic asthma: A molecular toxicological study on neuroimmune positive feedback mechanism - Xiaomin Xie; Yan Li; Biao Yan; Qi Peng; Runming Yao; Qihong Deng; Jinquan Li; Yang Wu; Shaohui Chen; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2024)

Biopolymer films incorporated with chlorogenic acid nanoparticles for active food packaging application - Kaixuan Ma; Fan Li; Taotao Zhe; Xinyu Sun; Xinyuan Zhang; Ping Wan; Huan Na; Junnan Zhao; Li Wang (Food Chemistry, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Thermocline stratification favors phytoplankton spatial overlap and species diversity in a subtropical deep reservoir - Li Wang; Jiarui Liu; Zhen Bao; Xufa Ma; Hong Shen; Ping Xie; Jun Chen (Science of The Total Environment, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Long-term tralopyril exposure results in endocrinological and transgenerational toxicity: A two-generation study of marine medaka (Oryzias melastigma) - Bin Liu; Ping Li; Ren-Yan Du; Cun-Long Wang; Yu-Qing Ma; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Science of The Total Environment, 2024)

Predictable shifts in diversity and ecosystem function in phytoplankton and zooplankton communities along thermocline stratification intensity continua - Li Wang; Jiarui Liu; Zhen Bao; Xufa Ma; Hong Shen; Jun Chen; Ping Xie (Science of The Total Environment, 2024)

Biomass ash chemistry in oxygen carrier aided combustion: Interaction between potassium and red mud - Yu Yang; Yali Shao; Shiwei Ma; Ping Li; Tao Song (Fuel, 2024)

Manganese-induced neurological pyroptosis: Unveiling the mechanism through the ROS activaed Caspase-3/GSDME signaling pathway - Jiacheng He; Xiaoli Ma; Jie Zhang; Yi-ping Yang; Huiyan Qin; Hao Chen; Shengtao Wei; Fangfei Li; Jian Wang; Guiqiang Liang; Yunfeng Zou (Food and Chemical Toxicology, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Define of Optimal Addition Period of Osteogenic Peptide to Accelerate the Osteogenic Differentiation of Human Pluripotent Stem Cells - Yameng Song; Hongjiao Li; Zixuan Wang; Jiamin Shi; Jing Li; Lu Wang; Lingzi Liao; Shengqin Ma; Yun Zhang; Bin Liu; Yaling Yang; Ping Zhou (Tissue Engineering and Regenerative Medicine, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

A novel microfluidic chip integrating with microcolumn array electrodes for rapid and ultrasensitive detection of alpha-fetoprotein - Shangshang Ma; Wei Zhao; Xutang Liu; Yifan Li; Ping Ma; Keying Zhang; Qing Zhang (Analytica Chimica Acta, 2024)

Probiotic Lactobacillus rhamnosus alleviates the neurotoxicity of microcystin-LR in zebrafish (Danio rerio) through the gut-brain axis - Ning Luan; Junli Zuo; Qianping Niu; Wei Yan; Tien-Chieh Hung; Haoling Liu; Qin Wu; Guoao Wang; Ping Deng; Xufa Ma; Jianhui Qin; Guangyu Li (Science of The Total Environment, 2024)

MnO2-RuO2/CFC composite electrode used in the treatment of high‑chlorine organic wastewater: Preparation, performance, mechanism and application feasibility - Nannan Wang; Liangwei Li; Weitao Ma; Zaixing Li; Xiaofei Chen; Qing Sun; Ping Chen; Bochao Liu (Journal of Water Process Engineering, 2024)

Exploring the formation and retention of aroma compounds in ready-to-eat roasted pork from four thermal methods: A lipidomics and heat transfer analysis - Huan Liu; Qianli Ma; Jiangtao Xing; Pi Li; Peng Gao; Nazimah Hamid; Zhongshuai Wang; Ping Wang; Hansheng Gong (Food Chemistry, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Dynamic assessment of dust hazard risk in the reconstruction of old industrial buildings: coupling effects of dust distribution and personnel trajectories - Wei Tian; Aoxiang Hu; Keyun Li; Ping Guo; Qing Chai; Ruihao Ma (Environmental Science and Pollution Research, 2023)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Ascendancy of pyraclostrobin nanocapsule formulation against Rhizoctonia solani: From a perspective of fungus - Li Ma; Meng Yu; Yingjian Ma; Linying Gao; Shouhe Pan; Xuefeng Li; Xuemin Wu; Yong Xu; Sen Pang; Ping Wang (Pesticide Biochemistry and Physiology, 2023)

Biotransformation of norethisterone by Rhizopus microsporus PT2906 - Xiulan Xin; Jia Liu; Shengqiao Luan; Meirong Zhou; Wenxin Wang; Yuzhuo Wu; Xiaochi Ma; Chao Wang; Ping Guo; Dawei Li (Phytochemistry Letters, 2023)

Study on seasonal floating treatment wetland combination water purification based on numerical simulation - Lanqing Qiu; Jiyuan Li; Ping Yu; Huixin Ma; Danying Li; Ai Wang (Journal of Water Process Engineering, 2023)

Review of thin-film resistor sensors: Exploring materials, classification, and preparation techniques - Zhenmin Li; Baosen Mi; Xun Ma; Ping Liu; Fengcang Ma; Ke Zhang; Xiaohong Chen; Wei Li (Chemical Engineering Journal, 2023)

Transposon-based identification of genes involved in the rimocidin biosynthesis in Streptomyces rimosus M527 - Hai-yue Bao; Hui-jie Li; Yong-yong Zhang; Andreas Bechthold; Xiao-ping Yu; Zheng Ma (World Journal of Microbiology and Biotechnology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Extraction and characterization of anti-virus anthraquinones from Nicotiana tabacum-derived Aspergillus oryzae YNCA1220 - Feng-Xian Yang; Yue-Yu Ma; Yu-Ping Wu; Gao-Kun Zhao; Yong-Ping Li; Zhen-Jie Li; Xue-Mei Li; Yin-Ke Li; Wei-Guang Wang; Min Zhou; Guang-Hui Kong; Qiu-Fen Hu (Pesticide Biochemistry and Physiology, 2023)

Co-application of chitooligosaccharides and arbuscular mycorrhiza fungi reduced greenhouse gas fluxes in saline soil by improving the rhizosphere microecology of soybean - Junqing Ma; Yi Xie; Jiali Sun; Ping Zou; Siqi Ma; Yuan Yuan; Shakeel Ahmad; Xia Yang; Changliang Jing; Yiqiang Li (Journal of Environmental Management, 2023)

Understanding the role of lipids in aroma formation of circulating non-fried roasted chicken using UHPLC-HRMS-based lipidomics and heat transfer analysis - Huan Liu; Dengyong Liu; Raheel Suleman; Peng Gao; Pi Li; Jiangtao Xing; Qianli Ma; Nazimah Hamid; Ping Wang; Hansheng Gong (Food Research International, 2023)

Abamectin induced brain and liver toxicity in carp: The healing potential of silybin and potential molecular mechanisms - Xinyu Wu; Yue Xin; Yeyun Ma; Kaixin Ping; Qiulu Li; Ying Sun; Zunhan Hu; Jingquan Dong (Fish & Shellfish Immunology, 2023)

Intense methane diffusive emissions in eutrophic urban lakes, Central China - Liuqing Zhang; Y. Jun Xu; Bingjie Ma; Ping Jiang; Siyue Li (Environmental Research, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Livestock wastes from family-operated farms are potential important sources of potentially toxic elements, antibiotics, and estrogens in rural areas in North China - Yang Li; Xinyu Li; Xupu Ma; Tianlei Qiu; Xincheng Fu; Zhihong Ma; Hua Ping; Cheng Li (Environmental Science and Pollution Research, 2023)

The long-term effects of thinning on soil respiration vary with season in subalpine spruce plantations - Long-Fei Chen; Zhi-Bin He; Wen-Zhi Zhao; Lei Ma; Sheng-En Liu; Li-Wen Zhao; Shu-Ping Yang; Xiang-Yan Feng (Agricultural and Forest Meteorology, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

Mediation of endoplasmic reticulum stress and NF-κB signaling pathway in DINP-exacerbated allergic asthma: A toxicological study with Balb/c mice - Fan Lei; Yang Wu; Chongyao Li; Biao Yan; Shaohui Chen; Qi Peng; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2023)

Constructing defective-functionalized g-C3N4 homojunction for efficient photocatalytic detoxification of lemon yellow in an aqueous solution and beverage - Shisen Li; Ping Liu; Yinghui Wang; Qingli Yang; Yongchao Ma (Food Chemistry, 2023)

Refining health risk assessment of arsenic in wild edible boletus from typical high geochemical background areas: The role of As species, bioavailability, and enterotoxicity - Mengying Li; Zheng Chen; Qing Xiong; Yunzhen Mu; Yumei Xie; Mengyan Zhang; Lena Q. Ma; Ping Xiang (Environmental Pollution, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

Spatiotemporal distribution, sources apportionment and ecological risks of PAHs: a study in the Wuhan section of the Yangtze River - Yulin Chen; Ranran Song; Ping Li; Yile Wang; Yang Tan; Yongfei Ma; Lie Yang; Li Wu; Zhenjie Du; Xuebin Qi; Zulin Zhang (Environmental Geochemistry and Health, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Dammarane-type saponins from Gynostemma pentaphyllum and their anti-aging activities via up-regulating mitochondria related proteins - Hai-Zhen Liang; Peng-Xin Lu; Li-Li Chu; Gang Li; Chuan-Biao Li; Xiao-Juan Chen; Jie Zhang; Juan Song; Tao Zhang; Ying Luo; Ying Hu; Bai-Ping Ma (Phytochemistry, 2023)

An ABCG-type transporter intensifies ametryn catabolism by Phase III reaction mechanism in rice - Yuxin Qiao; AI Ping Zhang; Li Ya Ma; Nan Zhang; Jintong Liu; Hong Yang (Journal of Hazardous Materials, 2023)

Effect of safflower oil and magnetic field-modified soy 11S globulin on rheological and emulsifying properties of oil-in-water emulsions - Zhuang-Li Kang; Jing-jie Xie; Zhong-liang Hu; Yan-ping Li; Han-Jun Ma (Food Hydrocolloids, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

COS and H2S simultaneous removal from blast furnace gas over a tailored Cu/Zr co-doped K@TiO2 bifunctional catalyst under low temperature - Xiang Li; Xueqian Wang; Li Yuan; Langlang Wang; Yixing Ma; You Wu; Yibing Xie; Rui Cao; Yiran Xiong; Ping Ning (Chemical Engineering Journal, 2023)

Inhibition of multiple uptake transporters in cardiomyocytes/mitochondria alleviates doxorubicin-induced cardiotoxicity - Yaodong Yi; Hengbin Zhang; Mingyang Chen; Binxin Chen; Yingchun Chen; Ping Li; Hui Zhou; Zhiyuan Ma; Huidi Jiang (Chemico-Biological Interactions, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Remediating petroleum hydrocarbons in highly saline–alkali soils using three native plant species - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yanhong Liu; Rong Ma; Ruijie Li; Leiping Shi (Journal of Environmental Management, 2023)

One-pot preparation of layered double oxides-engineered biochar for the sustained removal of tetracycline in water - Jiayi Tang; Yongfei Ma; Zhikang Deng; Ping Li; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Resveratrol and Sir2 Reverse Sleep and Memory Defects Induced by Amyloid Precursor Protein - Yuping Hao; Lingzhan Shao; Jianan Hou; Yan Zhang; Yuqian Ma; Jinhao Liu; Chuan Xu; Fujun Chen; Li-Hui Cao; Yong Ping (Neuroscience Bulletin, 2023)

Effect of stress induced damage on gas permeability of Beishan granite - Hai-Yang Zhang; Liang Chen; Jian Liu; Chun-Ping Wang; Li-Ke Ma; Wei Wang (European Journal of Environmental and Civil Engineering, 2023)

Identification of metabolites from edible mushroom Morchella sextelata and their biological evaluation - De-Xian Li; Xia Cheng; Fo-Pei Ma; Jie-Yu Chen; Yi-Ping Chen; Xiao-Shan Zhao; Qi Luo (Natural Product Research, 2023)

Real-time perception of rock–machine interaction information in TBM tunnelling using muck image analysis - Wei-Qiang Xie; Xiao-Ping Zhang; Xiao-Li Liu; Chen-Yu Xu; Xin-Fang Li; Dan-Qing Song; Qing Ma; Nan Hu (Tunnelling and Underground Space Technology, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

RNA-seq reveals the role of miR-223 in alleviating inflammation of bovine mammary epithelial cells - Yan-Xia Li; Peng Jiao; Xing-Ping Wang; Jin-Peng Wang; Fen Feng; Bin-Wu Bao; Yi-Wen Dong; Zhuo-Ma Luoreng; Da-Wei Wei (Research in Veterinary Science, 2023)

Three new isoquinoline alkaloids from the cigar tobacco-derived endophytic fungus Aspergillus felis - Yue-Yu Ma; Gui Pu; Xue-Ju Cha; Rui-Feng Xiong; Guang-Hai Zhang; Heng Yao; Mei-Fen Bao; Guang-Hui Kong; Yin-Ke Li; Qiu-Fen Hu; Yu-Ping Wu (Phytochemistry Letters, 2023)

Nanoencapsulation-based fabrication of eco-friendly pH-responsive pyraclostrobin formulations with enhanced photostability and adhesion to leaves - Yingjian Ma; Linjie Li; Rui Zhao; Zhe Sun; Yinmin Wang; Meng Yu; Shouhe Pan; Xinyu Guo; Yong Xu; Hongmei Wang; Ping Wang; Xuemin Wu (Journal of Environmental Chemical Engineering, 2023)

A transcriptional atlas of the silk gland in Antheraea pernyi revealed by IsoSeq - Jianping Duan; Shanshan Li; Zhengtian Zhang; Lunguang Yao; Xinfeng Yang; Sanyuan Ma; Nini Duan; Jiazhen Wang; Xuwei Zhu; Ping Zhao (Journal of Asia-Pacific Entomology, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Cu/ACF adsorbent modified by non-thermal plasma for simultaneous adsorption–oxidation of H2S and PH3 - Xinyu Yang; Kai Li; Chi Wang; Fei Wang; Xin Sun; Yixing Ma; Yuan Li; Lei Shi; Ping Ning (Journal of Environmental Sciences, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Synergistic Apoptosis-Ferroptosis: Oxaliplatin loaded amorphous iron oxide nanoparticles for High-efficiency therapy of orthotopic pancreatic cancer and CA19-9 levels decrease - Yilong Li; Xinlong Wang; Binbin Ding; Cong He; Can Zhang; Jiating Li; Haonian Wang; Zhibo Li; Gang Wang; Yongwei Wang; Hua Chen; Ping'an Ma; et al. (Chemical Engineering Journal, 2023)

A genome-wide co-expression network analysis revealed ZmNRAMP6-mediated regulatory pathway involved in maize tolerance to lead stress - Peng Liu; Li Jiang; Ping Long; Qinglin Li; Fengxia Hou; Guangsheng Yuan; Zhong Chen; Minyan Zhang; Chaoying Zou; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2023)

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

Experimental study on in-cylinder combustion and exhaust emissions characteristics of natural gas/diesel dual-fuel engine with single injection and split injection strategies - Junheng Liu; Xuchao Zhang; Yuan Liu; Ping Sun; Qian Ji; Xidong Wang; Zhipeng Li; Hongjie Ma (Process Safety and Environmental Protection, 2023)

Effects of pre-emulsified safflower oil with magnetic field modified soy 11S globulin on the gel, rheological, and sensory properties of reduced-animal fat pork batter - Zhuang-Li Kang; Jing-jie Xie; Yan-ping Li; Wan-jie Song; Han-Jun Ma (Meat Science, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

Periploca sepium leaf dry weight, area, and thickness scale differently under different light environments in Taohe riparian forests - Min Ma; Cheng-Zhang Zhao; Man-Ping Kang; Xiao-Ya Li; Zhi-Wei Zhang; Xu-Qian Bai (Flora, 2023)

Effects of different crop rotations on the incidence of cotton Verticillium wilt and structure and function of the rhizospheric microbial community - Weisong Zhao; Shezeng Li; Lihong Dong; Peipei Wang; Xiuyun Lu; Xiaoyun Zhang; Zhenhe Su; Qinggang Guo; Ping Ma (Plant and Soil, 2023)

Promising roles of non-exosomal and exosomal non-coding RNAs in the regulatory mechanism and as diagnostic biomarkers in myocardial infarction - Jingru Li; Haocheng Ma; Xinyu Wu; Guihu Sun; Ping Yang; Yunzhu Peng; Qixian Wang; Luqiao Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Source apportionment of heavy metals in soils around a coal gangue heap with the APCS-MLR and PMF receptor models in Chongqing, southwest China - Jie Ma; Zhi-jie Shen; Sheng-lan Wang; Li Deng; Jing Sun; Ping Liu; Ze-lei She (Journal of Mountain Science, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Di-n-butyl phthalate stress induces changes in the core bacterial community associated with nitrogen conversion during agricultural waste composting - Ping Wang; Jing Ma; Lixin Wang; Linfan Li; Xinyu Yan; Ruyi Zhang; Tomislav Cernava; Decai Jin (Journal of Hazardous Materials, 2023)

Automatic detection of river capture based on planform pattern and χ-plot of the stream network - Qi-Yuan Ma; An-Bo Li; Ping Wang (Geomorphology, 2023)

Developing a hydroxyl-functionalized magnetic porous organic polymer combined with HPLC-MS/MS for determining 31 amide herbicides in fruit wine - Can Zhang; Shuo Li; Jing Wu; Tengteng Ping; Ling Ma; Ke Wang; Kaoqi Lian (Food Chemistry, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Source characterization of volatile organic compounds in urban Beijing and its links to secondary organic aerosol formation - Quan Liu; Jiujiang Sheng; Yangzhou Wu; Zhiqiang Ma; Junying Sun; Ping Tian; Delong Zhao; Xia Li; Kang Hu; Siyuan Li; Xiaojing Shen; Yangmei Zhang; et al. (Science of The Total Environment, 2023)

Heavy metal(loid)s in agricultural soil from main grain production regions of China: Bioaccessibility and health risks to humans - Cheng-Chen Wang; Qiao-Chu Zhang; Shao-Guo Kang; Meng-Ying Li; Meng-Yan Zhang; Wu-Mei Xu; Ping Xiang; Lena Q. Ma (Science of The Total Environment, 2023)

Self-diffusion coefficient and sound velocity of Fe-Ni-O fluid: Implications for the stratification of Earth's outer core - Wei-Jie Li; Zi Li; Chong-Jie Mo; Zhe Ma; Xian-Tu He; Cong Wang; Ping Zhang (Physics of the Earth and Planetary Interiors, 2023)

A novel exposure mode based on UVA-LEDs for bacterial inactivation - Ning Zhao; Li-Ping Lv; Ping Ma; Yang-Yang Zhang; Jiang Deng; Yan-Yu Zhang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Research on the hydrothermal regeneration of powdered activated coke in wastewater treatment - Zhanyao Li; Guifang Chen; Huiru Ma; Fuyu Huang; Hao Xu; Liqiang Zhang; Xueliang Yuan; Xinyan Zhang; Shouyan Chen; Ping Zhou (Journal of Environmental Chemical Engineering, 2023)

Bi/Te control on gold mineralizing processes in the North China Craton: Insights from the Wulong gold deposit - Haoxuan Feng; Ping Shen; Rixiang Zhu; Andrew G. Tomkins; Joël Brugger; Ge Ma; Changhao Li; Yang Wu (Mineralium Deposita, 2023)

Genome-wide characterization of Alfin-like (AL) genes in apple and functional identification of MdAL4 in response to drought stress - Ping Wang; Shixiong Lu; Wenfang Li; Zonghuan Ma; Juan Mao; Baihong Chen (Plant Cell Reports, 2023)

Catalysts for gaseous organic sulfur removal - Yuxuan Xie; Jiacheng Bao; Xin Song; Xin Sun; Ping Ning; Chi Wang; Fei Wang; Yixing Ma; Maohong Fan; Kai Li (Journal of Hazardous Materials, 2023)

Laboratory Investigations into the Failure Mechanisms of New Yielding and Inflatable Rockbolts Under Axial and Shearing Loading Conditions - Danqi Li; Shuqi Ma; Martin Lane; Ping Chang; Brendan Crompton; Simon Alexander Hagen (Rock Mechanics and Rock Engineering, 2023)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Association between short-term exposure to ambient air pollution and number of outpatient Helicobacter pylori infection visits - Lizuo Ma; Zhijing Lin; Jiaoxue Wang; Ruirui Ye; Yuefang Li; Ping Chen; Zhi Yuan; Liyan Yang; Lin Miao; Jiehua Li (Environmental Science and Pollution Research, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Precise ages of gold mineralization and pre-gold hydrothermal activity in the Baiyun gold deposit, northeastern China: in situ U–Pb dating of hydrothermal xenotime and rutile - Haoxuan Feng; Ping Shen; Rixiang Zhu; Jian-Wei Zi; David I. Groves; Changhao Li; Yang Wu; Ge Ma; Taiyang Li (Mineralium Deposita, 2022)

Monitoring and control methods of harmful algal blooms in Chinese freshwater system: a review - Shengjun Xu; Ping Lyu; Xiaoxu Zheng; Haijun Yang; Bing Xia; Hui Li; Hao Zhang; Shuanglong Ma (Environmental Science and Pollution Research, 2022)

Design and synthesis of ludartin derivatives as potential anticancer agents against hepatocellular carcinoma - Jin-Jin Sun; Jin-Ping Wang; Tian-Ze Li; Yun-Bao Ma; Dong Xue; Ji-Jun Chen (Medicinal Chemistry Research, 2022)

The α5-nAChR/PD-L1 axis facilitates lung adenocarcinoma cell migration and invasion - Ping Zhu; Guiyu Kang; Yang Jiao; Chengzhi Gui; Huiping Fan; Xiangying Li; Yanfei Jia; Lulu Zhang; Xiaoli Ma (Human Cell, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Logging calculation method and application of geochemical parameters of source rocks with different lithologies in marine-continental transitional facies in Ordos Basin, China - Li Ping Zhao; Jungang Lu; Xiaogang Li; Yong Li; Qingbo He; Zhiwei Ma (Arabian Journal of Geosciences, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Transcriptomic analyses reveal the effect of nitric oxide on the lateral root development and growth of mangrove plant Kandelia obovata - Ming-Yue Wei; Huan Li; You-Hui Zhong; Zhi-Jun Shen; Dong-Na Ma; Chang-Hao Gao; Yi-Ling Liu; Wen-Hua Wang; Jing-Ya Zhang; Yan-Ping You; Hai-Lei Zheng (Plant and Soil, 2022)

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

A comparison of the reproducibility of regional precipitation properties simulated respectively by weather generators and stochastic simulation methods - Luhua Yang; Ping-an Zhong; Feilin Zhu; Yufei Ma; Han Wang; Jieyu Li; Chengjing Xu (Stochastic Environmental Research and Risk Assessment, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Responses of ecosystem respiration, methane uptake and nitrous oxide emission to drought in a temperate desert steppe - Ping Yue; Xiaoan Zuo; Kaihui Li; Xiangyun Li; Shaokun Wang; Xujun Ma; Hao Qu; Min Chen; Liangxu Liu; Tom Misselbrook; Qiang Yu (Plant and Soil, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Design and Evaluation of a Novel Transversal Double-bud Sugarcane Planter with Seed Pre-cutting - Jia-Qin Zhong; Li-Min Tao; Shang-Ping Li; Fang-Lan Ma; Yuan-Ling Chen (Sugar Tech, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Cloud-Based Multidimensional Parallel Dynamic Programming Algorithm for a Cascade Hydropower System - Yufei Ma; Ping-an Zhong; Bin Xu; Feilin Zhu; Jieyu Li; Han Wang; Qingwen Lu (Water Resources Management, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

The roles of NLRP3 inflammasome-mediated signaling pathways in hyperuricemic nephropathy - Li Wen; Hongliu Yang; Liang Ma; Ping Fu (Molecular and Cellular Biochemistry, 2021)

The Biological Role of Optimized Recombinant Oral Long-Acting Glucagon Like Peptide-1 and Its Impact on the Expression of Genes Associated with Glucose Metabolism of Diabetes - Shan He; Jie Zhang; Tao Wang; Ping Wu; Jianyun Liu; Minggang Li; Baicheng Ma (International Journal of Peptide Research and Therapeutics, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Improved Oral Bioavailability and Hypolipidemic Effect of Syringic Acid via a Self-microemulsifying Drug Delivery System - Congyong Sun; Wenjing Li; Huiyun Zhang; Michael Adu-Frimpong; Ping Ma; Yuan Zhu; Wenwen Deng; Jiangnan Yu; Ximing Xu (AAPS PharmSciTech, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Tau Accumulation via Reduced Autophagy Mediates GGGGCC Repeat Expansion-Induced Neurodegeneration in Drosophila Model of ALS - Xue Wen; Ping An; Hexuan Li; Zijian Zhou; Yimin Sun; Jian Wang; Lixiang Ma; Boxun Lu (Neuroscience Bulletin, 2020)

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

MdHAL3, a 4′-phosphopantothenoylcysteine decarboxylase, is involved in the salt tolerance of autotetraploid apple - Shuang Yang; Feng Zhang; Yangshu Wang; Hao Xue; Qiu Jiang; Jiajun Shi; Hongyan Dai; Zhihong Zhang; Linguang Li; Ping He; Yuanyuan Li; Yue Ma (Plant Cell Reports, 2020)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Integrated biomarker parameters response to the toxic effects of high stocking density, CuSO4, and trichlorfon on fish and protective role mediated by Angelica sinensis extract - HuaTao Li; YuTing Ma; Ying Liu; Min Wu; Jiao Long; XiaoQin Jing; SiShun Zhou; Ping Yuan; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Sandstorm weather is a risk factor for mortality in ischemic heart disease patients in the Hexi Corridor, northwestern China - Xinghui Li; Hui Cai; Xiaolan Ren; Jin He; Jia Tang; Ping Xie; Nan Wang; Fangfei Nie; Linfeng Lei; Chenchen Wang; Wenli Li; Jing Ma (Environmental Science and Pollution Research, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Qualitative and Quantitative Analyses of the Colonization Characteristics of Bacillus subtilis Strain NCD-2 on Cotton Root - Lihong Dong; Qinggang Guo; Peipei Wang; Xiaoyun Zhang; Zhenhe Su; Weisong Zhao; Xiuyun Lu; Shezeng Li; Ping Ma (Current Microbiology, 2020)

Targeting human cytomegalovirus IE genes by CRISPR/Cas9 nuclease effectively inhibits viral replication and reactivation - Jun Xiao; Jiang Deng; Qian Zhang; Ping Ma; Liping Lv; Yangyang Zhang; Cuiying Li; Yanyu Zhang (Archives of Virology, 2020)

Duration of SARS-CoV-2 viral shedding during COVID-19 infection - Guo-Qing Qian; Xue-Qin Chen; Ding-Feng Lv; Ada Hoi Yan Ma; Li-Ping Wang; Nai-Bin Yang; Xiao-Min Chen (Infectious Diseases, 2020)

Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations - Hong-Bo Li; Meng-Ya Li; Di Zhao; Jie Li; Shi-Wei Li; Ping Xiang; Albert L. Juhasz; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Study on chemical constituents of an edible mushroom Volvariella volvacea and their antitumor activity in vitro - Ping Chen; Hui-Juan Qin; Yuan-Wei Li; Guo-Xu Ma; Jun-Shan Yang; Qi Wang (Natural Product Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

Restricted nitrous oxide emissions by ammonia oxidizers in two agricultural soils following excessive urea fertilization - Zhaoming Chen; Qiang Wang; Jun Zhao; Yudong Chen; Huoyan Wang; Junwei Ma; Ping Zou; Li Bao (Journal of Soils and Sediments, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Relative energy zero ratio-based approach for identifying pulse-like ground motions - Ping Liu; Ning Li; Hua Ma; Lili Xie; Baofeng Zhou (Earthquake Engineering and Engineering Vibration, 2020)

Ultrahigh Temperature Metamorphic Record of Pelitic Granulites in the Huangtuyao Area of the Huai’an Complex, North China Craton - Shaoting Ma; Xu-Ping Li; Hao Liu; Fanmei Kong; Han Wang (Journal of Earth Science, 2019)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Flood scaling under nonstationarity in Daqinghe River basin, China - Jianzhu Li; Qiushuang Ma; Yu Tian; Yuming Lei; Ting Zhang; Ping Feng (Natural Hazards, 2019)

Assessment of slope construction risk uncertainty based on index importance ranking - Daming Lin; Ping Chen; Jilei Ma; Yun Zhao; Tao Xie; Renmao Yuan; Lin Li (Bulletin of Engineering Geology and the Environment, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Molecular detection and identification of phytoplasmas in a novel 16SrI subgroup in sunflowers and cocklebur weeds - Lei Zhang; Ping-ping Sun; Qiang Ma; Xiao-zhao Xu; Hong-you Zhou; Zheng-nan Li (Journal of Plant Pathology, 2019)

Suppression of winter heavy precipitation in Southeastern China by the Kuroshio warm current - Guangzhi Xu; Ping Chang; Xiaohui Ma; Mingkui Li (Climate Dynamics, 2019)

Relationship between stand characteristics and soil properties of two typical forest plantations in the mountainous area of Western Sichuan, China - Hao Yang; Ning Miao; Shao-cai Li; Rui Ma; Zi-yan Liao; Wei-ping Wang; Hai-long Sun (Journal of Mountain Science, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Study on Stability of Goaf Pillars in Daqiao Phosphate Mine: Theoretical Calculation and Field Investigation - Feifei Wang; Ping Zou; Zhonghua Meng; Aibing Li; Zhengyu Liu; Wanjie Hu; Zeng Ma (Geotechnical and Geological Engineering, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Evolution of pore-size distribution of intact loess and remolded loess due to consolidation - Jia-Ding Wang; Ping Li; Yan Ma; Sai K. Vanapalli (Journal of Soils and Sediments, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Estimation of above-ground biomass of reed (Phragmites communis) based on in situ hyperspectral data in Beijing Hanshiqiao Wetland, China - Wei Li; Zhiguo Dou; Yan Wang; Gaojie Wu; Manyin Zhang; Yinru Lei; Yunmei Ping; Jiachen Wang; Lijuan Cui; Wu Ma (Wetlands Ecology and Management, 2019)

Plantlet regeneration from primary callus cultures of Lilium brownii F.E.Br. ex Miellez var. giganteum G. Y. Li & Z. H. Chen, a rare bulbous germplasm - Yun Wu; Yi-Di Ma; Yue Li; Lin Zhang; Yi-Ping Xia (In Vitro Cellular & Developmental Biology - Plant, 2019)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

Hazard zoning of trunk highway slope disasters: a case study in northern Shaanxi, China - Huan Zhao; Wei-Ping Tian; Jia-chun Li; Bao-Cheng Ma (Bulletin of Engineering Geology and the Environment, 2018)

Anodal Transcranial Direct-Current Stimulation Over the Right Dorsolateral Prefrontal Cortex Influences Emotional Face Perception - Li-Chuan Yang; Ping Ren; Yuan-Ye Ma (Neuroscience Bulletin, 2018)

Divergence in larval diapause induction between the rice and water-oat populations of the striped stem borer, Chilo suppressalis (Walker) (Lepidoptera: Crambidae) - Yuan Zhou; Dan Sun; Wei-Li Quan; Nan Ding; Wen Liu; Wei-Hua Ma; Xiao-Ping Wang (Environmental Science and Pollution Research, 2018)

Source identification of PAHs in soils based on stable carbon isotopic signatures - Peng Gao; Hongbo Li; Chris P. Wilson; Timothy G. Townsend; Ping Xiang; Yungen Liu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2018)

Recent advances in rapid pathogen detection method based on biosensors - Ying Chen; Zhenzhen Wang; Yingxun Liu; Xin Wang; Ying Li; Ping Ma; Bing Gu; Hongchun Li (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Submarine landslide identified in DLW3102 core of the northern continental slope, South China Sea - Yuanqin Xu; Lejun Liu; Hang Zhou; Baoqi Huang; Ping Li; Xiudong Ma; Feiyin Dong (Journal of Ocean University of China, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

Effect of Fe3O4 nanoparticles on Sphingobium yanoikuyae XLDN2-5 cells in carbazole biodegradation - Huihui Sun; Hanyue Ma; Zhuang Liu; Yufei Li; Ping Xu; Xia Wang (Nanotechnology for Environmental Engineering, 2017)

Association between SSR markers and fibre traits in sea island cotton (Gossypium barbadense) germplasm resources - QI MA; JING ZHAO; HAI LIN; XINZHU NING; PING LIU; FUJUN DENG; AIJUN SI; JILIAN LI (Journal of Genetics, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

Oxidation of indometacin by ferrate (VI): kinetics, degradation pathways, and toxicity assessment - Junlei Huang; Yahui Wang; Guoguang Liu; Ping Chen; Fengliang Wang; Jingshuai Ma; Fuhua Li; Haijin Liu; Wenying Lv (Environmental Science and Pollution Research, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Di (2-ethylhexyl) phthalate impairs steroidogenesis in ovarian follicular cells of prepuberal mice - Fang-Nong Lai; Jing-Cai Liu; Lan Li; Jun-Yu Ma; Xue-Lian Liu; Yu-Ping Liu; Xi-Feng Zhang; Hong Chen; Massimo De Felici; Paul W. Dyce; Wei Shen (Archives of Toxicology, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Fine mapping and candidate gene analysis of two loci conferring resistance to Phytophthora sojae in soybean - Linghong Li; Feng Lin; Weidong Wang; Jieqing Ping; Joshua C. Fitzgerald; Meixia Zhao; Shuai Li; Lianjun Sun; Chunmei Cai; Jianxin Ma (Theoretical and Applied Genetics, 2016)

Thrombospondin-4 Promotes Neuronal Differentiation of NG2 Cells via the ERK/MAPK Pathway - Hai Jie Yang; Shuang Ping Ma; Fei Ju; Ya Ping Zhang; Zhi Chao Li; Bin Bin Zhang; Jun Jiang Lian; Lei Wang; Bin Feng Cheng; Mian Wang; Zhi Wei Feng (Journal of Molecular Neuroscience, 2016)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Development of a stationary carbon emission inventory for Shanghai using pollution source census data - Xianzhe Li; Ping Jiang; Yan Zhang; Weichun Ma (Frontiers of Earth Science, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Risk assessment of dietary exposure to aluminium in the Chinese population - Ning Ma; Zhao-Ping Liu; Da-Jin Yang; Jiang Liang; Jiang-Hui Zhu; Hai-Bin Xu; Feng-Qin Li; Ning Li (Food Additives & Contaminants: Part A, 2016)

Hydrogen peroxide is involved in abscisic acid-induced adventitious rooting in cucumber (Cucumis sativus L.) under drought stress - Xue-Ping Li; Qing-Qing Xu; Wei-Biao Liao; Zhan-Jun Ma; Xiao-Ting Xu; Meng Wang; Peng-Ju Ren; Li-Juan Niu; Xin Jin; Yong-Chao Zhu (Journal of Plant Biology, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

A New Methodology for Open Pit Slope Design in Karst-Prone Ground Conditions Based on Integrated Stochastic-Limit Equilibrium Analysis - Ke Zhang; Ping Cao; Guowei Ma; Wenchen Fan; Jingjing Meng; Kaihui Li (Rock Mechanics and Rock Engineering, 2016)

Stability Analysis of Rock Slope Controlled by Major Geological Discontinuities Based on the Extended Kinematical Element Method - Ke Zhang; Ping Cao; Guowei Ma; Feng Ren; Kaihui Li (Rock Mechanics and Rock Engineering, 2016)

Photodegradation of gemfibrozil in aqueous solution under UV irradiation: kinetics, mechanism, toxicity, and degradation pathways - Jingshuai Ma; Wenying Lv; Ping Chen; Yida Lu; Fengliang Wang; Fuhua Li; Kun Yao; Guoguang Liu (Environmental Science and Pollution Research, 2016)

Imbalanced expression of Bcl-xL and Bax in platelets treated with plasma from immune thrombocytopenia - Jianlin Qiao; Yun Liu; Depeng Li; Yulu Wu; Xiaoqian Li; Yao Yao; Mingshan Niu; Chunling Fu; Hongchun Li; Ping Ma; Zhenyu Li; Kailin Xu; et al. (Immunologic Research, 2016)

TLR3 and TLR4 as potential clinical biomarkers for in-stent restenosis in drug-eluting stents patients - Shao Liang; Ma Aiqun; Li Jiwu; Zhang Ping (Immunologic Research, 2016)

Elevated expression of NLRP3 in patients with immune thrombocytopenia - Jianlin Qiao; Yun Liu; Xiaoqian Li; Yuan Xia; Yulu Wu; Depeng Li; Hongchun Li; Ping Ma; Feng Zhu; Zhenyu Li; Kailin Xu; Lingyu Zeng (Immunologic Research, 2016)

Adverse effect of DEHP exposure on the serum insulin level of Balb/c mice - Jing Wang; Jinquan Li; Kashif Rafiq Zahid; Kun Wang; Yan Qian; Ping Ma; Shumao Ding; Xu Yang; Xianliang Wang (Molecular & Cellular Toxicology, 2016)

Prediction of drug-induced eosinophilia adverse effect by using SVM and naïve Bayesian approaches - Hui Zhang; Peng Yu; Ming-Li Xiang; Xi-Bo Li; Wei-Bao Kong; Jun-Yi Ma; Jun-Long Wang; Jin-Ping Zhang; Ji Zhang (Medical & Biological Engineering & Computing, 2016)

A Phytocystatin Gene from Malus prunifolia (Willd.) Borkh., MpCYS5, Confers Salt Stress Tolerance and Functions in Endoplasmic Reticulum Stress Response in Arabidopsis - Yanxiao Tan; Xiaoyu Wei; Ping Wang; Xun Sun; Mingjun Li; Fengwang Ma (Plant Molecular Biology Reporter, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

The Adsorption and Desorption of Pb2+ and Cd2+ in Freeze–Thaw Treated Soils - Linhui Li; Jincai Ma; Meng Xu; Xu Li; Jiahui Tao; Guanzhu Wang; Jitong Yu; Ping Guo (Bulletin of Environmental Contamination and Toxicology, 2016)

The isoforms generated by alternative translation initiation adopt similar conformation in the selectivity filter in TREK-2 - Ren-Gong Zhuo; Peng Peng; Xiao-Yan Liu; Shu-Zhuo Zhang; Jiang-Ping Xu; Jian-Quan Zheng; Xiao-Li Wei; Xiao-Yun Ma (Journal of Physiology and Biochemistry, 2015)

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

Assessment of Sediment Risk in the North End of Tai Lake, China: Integrating Chemical Analysis and Chronic Toxicity Testing with Chironomus dilutus - Hongxue Qi; Ping Ma; Huizhen Li; Jing You (Archives of Environmental Contamination and Toxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Characteristics and distribution patterns of reef complexes on the carbonate platform margin in deep water areas: the western South China Sea - Ping Chen; Xushen Li; Yahui Wang; Yongchao Lu; Zehong Zhong; Lei Chen; Qianmei Zuo; Yiquan Ma; Chao Wang; Xuebin Du (Acta Oceanologica Sinica, 2015)

Roles of Serine/Threonine Phosphatases in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Jing Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Functions for the cAMP/Epac/Rap1 Signaling Pathway in Low-Dose Endothelial Monocyte-Activating Polypeptide-II-Induced Opening of Blood–Tumor Barrier - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Ping Wang; Li-bo Liu; Yi-long Yao; Jun Ma (Journal of Molecular Neuroscience, 2015)

Comparative proteomic analysis of silkworm fat body after knocking out fibroin heavy chain gene: a novel insight into cross-talk between tissues - Quanmei Chen; Zhengang Ma; Xin Wang; Zhiqing Li; Yan Zhang; Sanyuan Ma; Ping Zhao; Qingyou Xia (Functional & Integrative Genomics, 2015)

Quantitative Analysis of the Migration and Accumulation of Bacillus subtilis in Asparagus officinalis - Bian-Qing Hao; Li-Ping Ma; Xiong-Wu Qiao (Current Microbiology, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

Contribution of mitochondrial function to exercise-induced attenuation of renal dysfunction in spontaneously hypertensive rats - Qi Gu; Li Zhao; Yan-Ping Ma; Jian-Dong Liu (Molecular and Cellular Biochemistry, 2015)

Phototransformation of mefenamic acid induced by nitrite ions in water: mechanism, toxicity, and degradation pathways - Ping Chen; Wenying Lv; Zhiming Chen; Jingshuai Ma; Ruobai Li; Kun Yao; Guoguang Liu; Fuhua Li (Environmental Science and Pollution Research, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Two new triterpenoid saponins obtained by microbial hydrolysis with Alternaria alternata AS 3.6872 - Li-Hua Mu; Yong-Jie Gu; Bai-Ping Ma; Li Lu; Ping Liu (Natural Product Research, 2015)

Caveolin-1 mediates gene transfer and cytotoxicity of polyethyleneimine in mammalian cell lines - Hai-Jie Yang; Pei Feng; Lei Wang; Zhi-Chao Li; Shuang-Ping Ma; Mian Wang; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2015)

Blood–brain barrier permeability change and regulation mechanism after subarachnoid hemorrhage - Zhiqing Li; Guobiao Liang; Teng Ma; Jingchen Li; Ping Wang; Libo Liu; Bo Yu; Yunhui Liu; Yixue Xue (Metabolic Brain Disease, 2015)

Serine/Threonine-Protein Kinase PFTK1 Modulates Oligodendrocyte Differentiation via PI3K/AKT Pathway - Hai Jie Yang; Lei Wang; Mian Wang; Shuang Ping Ma; Bin Feng Cheng; Zhi Chao Li; Zhi Wei Feng (Journal of Molecular Neuroscience, 2015)

Optimization of Astragalus membranaceus hairy roots induction and culture conditions for augmentation production of astragalosides - Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Wei Ma; Li-Ping Yao; Chen Feng; Xin-Xin Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Identification of Mycoplasma suis MSG1 interaction proteins on porcine erythrocytes - Yaning Zhang; Yao Zou; Peipei Ma; Hassan Mushtaq Muhammad; Yufeng Li; Ping Jiang (Archives of Microbiology, 2015)

Free radical-scavenging activities of oligomeric proanthocyanidin from Rhodiola rosea L. and its antioxidant effects in vivo - Qian Zhou; Zhi-Ping Yin; Lei Ma; Wen Zhao; Hong-Wei Hao; Hui-Ling Li (Natural Product Research, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Unsupervised change detection based on robust chi-squared transform for bitemporal remotely sensed images - Aiye Shi; Du Q. Huynh; Feng Chen Huang; Shao Hong Shen; Wen Ping Lu; Zhen Li Ma (International Journal of Remote Sensing, 2014)

Soil bacterial communities of different natural forest types in Northeast China - Hui Li; Dandan Ye; Xugao Wang; Matthew Lee Settles; Jun Wang; Zhanqing Hao; Lisha Zhou; Ping Dong; Yong Jiang; Zhanshan Ma (Plant and Soil, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Biofilm Formation of Streptococcus equi ssp. zooepidemicus and Comparative Proteomic Analysis of Biofilm and Planktonic Cells - Li Yi; Yang Wang; Zhe Ma; Hui Zhang; Yue Li; Jun-xi Zheng; Yong-chun Yang; Hong-jie Fan; Cheng-ping Lu (Current Microbiology, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Development and validation of molecular markers closely linked to the wheat stripe rust resistance gene YrC591 for marker-assisted selection - Hongxing Xu; Jie Zhang; Ping Zhang; Yanmin Qie; Yongchun Niu; Hongjie Li; Pengtao Ma; Yunfeng Xu; Diaoguo An (Euphytica, 2014)

Wnt-promoted Isl1 expression through a novel TCF/LEF1 binding site and H3K9 acetylation in early stages of cardiomyocyte differentiation of P19CL6 cells - Huafei Lu; Yanming Li; Yang Wang; Yinan Liu; Weiping Wang; Zhuqing Jia; Ping Chen; Kangtao Ma; Chunyan Zhou (Molecular and Cellular Biochemistry, 2014)

Haplotype analysis of TLR4 gene and its effects on milk somatic cell score in Chinese commercial cattle - Xing Ping Wang; Zhuo Ma Luoreng; Shu Xin Gao; Dong Sheng Guo; Jun Ya Li; Xue Gao; Shang Zhong Xu; Feng Li; Gang Chen; Jin Ren Wang (Molecular Biology Reports, 2014)

Statistical analysis of sudden chemical leakage accidents reported in China between 2006 and 2011 - Yang Li; Hua Ping; Zhi-Hong Ma; Li-Gang Pan (Environmental Science and Pollution Research, 2014)

Antitumor Activity of Gemcitabine Can Be Potentiated in Pancreatic Cancer through Modulation of TLR4/NF-κB signaling by 6-Shogaol - Ling Zhou; Lianwen Qi; Lifeng Jiang; Ping Zhou; Jiang Ma; Xiaojun Xu; Ping Li (The AAPS Journal, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Mas-related G protein-coupled receptor D is coupled to endogenous calcium-activated chloride channel in Xenopus oocytes - Ren-Gong Zhuo; Xiao-Yun Ma; Pei-Lan Zhou; Xiao-Yan Liu; Kang Zhang; Xiao-Li Wei; Hai-Tao Yan; Jiang-Ping Xu; Jian-Quan Zheng (Journal of Physiology and Biochemistry, 2014)

Advanced glycation end products impair KCa3.1- and KCa2.3-mediated vasodilatation via oxidative stress in rat mesenteric arteries - Li-Mei Zhao; Yan Wang; Xiao-Zhen Ma; Nan-Ping Wang; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2014)

Three Novel SNPs in the Coding Region of the Bovine MC3R Gene and Their Associations with Growth Traits - Zhuo Ma Luoreng; Xing Ping Wang; Yun Ma; Feng Li; Dong Sheng Guo; Na Li; Jin Ren Wang (Biochemical Genetics, 2014)

Identification of miR-1293 potential target gene: TIMP-1 - Ping Li; Yunyun Ma; Yuanyuan Wang; Tengfei Chen; Huaqi Wang; Heying Chu; Guoqiang Zhao; Guojun Zhang (Molecular and Cellular Biochemistry, 2013)

Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue Hui Ma (Tropical Animal Health and Production, 2013)

The HTLV-1 HBZ protein inhibits cyclin D1 expression through interacting with the cellular transcription factor CREB - Yunyun Ma; Shangen Zheng; Yuanyuan Wang; Wenqiao Zang; Min Li; Na Wang; Ping Li; Jing Jin; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Discrimination between Demodex folliculorum (Acari: Demodicidae) isolates from China and Spain based on mitochondrial cox1 sequences - Ya-e Zhao; Jun-xian Ma; Li Hu; Li-ping Wu; Manuel De Rojas (Journal of Zhejiang University-SCIENCE B, 2013)

Absolute Quantification of E1, Ubiquitin-Like Proteins and Nedd8–MLN4924 Adduct by Mass Spectrometry - Xiaofeng Yang; James E. Brownell; Qing Xu; Fengying Zhu; Jingya Ma; Huay-Keng Loke; Neil Rollins; Teresa A. Soucy; James J. Minissale; Michael P. Thomas; William D. Mallender; Lawrence R. Dick; et al. (Cell Biochemistry and Biophysics, 2013)

New kaurene diterpenoid glycosides from fenugreek seeds - Xu Pang; Li-Ping Kang; He-Shui Yu; Yang Zhao; Cheng-Qi Xiong; Jie Zhang; Bai-Ping Ma (Natural Product Research, 2013)

Molecular characterization and phylogenetic analysis of infectious bursal disease viruses isolated from chicken in South China in 2011 - Di Liu; Xiang-Bin Zhang; Zhuan-Qiang Yan; Feng Chen; Jun Ji; Jian-Ping Qin; Hai-Yan Li; Jun-Peng Lu; Yu Xue; Jia-Jia Liu; Qing-Mei Xie; Jing-Yun Ma; et al. (Tropical Animal Health and Production, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Function of the anal sacs and mid-gut in mitochondrial sulphide metabolism in the echiuran worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Li-Tao Zhang; Xiao-Li Shi; Ying-Ping Dong (Marine Biology Research, 2012)

Genetic polymorphisms of lipoprotein lipase gene and their associations with growth traits in Xiangxi cattle - Xing Ping Wang; Zhuo Ma Luoreng; Feng Li; Jin Ren Wang; Na Li; Shu Hong Li (Molecular Biology Reports, 2012)

Evolutionary rate of human tissue-specific genes are related with transposable element insertions - Ping Jin; Sheng Qin; Xi Chen; Yumei Song; Jesse Li-Ling; Xiaofeng Xu; Fei Ma (Genetica, 2012)

Response of Sulfide:Quinone Oxidoreductase to Sulfide Exposure in the Echiuran Worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Xiao-Li Shi; Ying-Ping Dong; Jin-Long Li (Marine Biotechnology, 2012)

A meta-analysis of association between acne vulgaris and Demodex infestation - Ya-e Zhao; Li Hu; Li-ping Wu; Jun-xian Ma (Journal of Zhejiang University-SCIENCE B, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry - Ping He; Yue Ma; Hongyan Dai; Linguang Li; Yuexue Liu; He Li; Guiling Zhao; Zhihong Zhang (Journal of Plant Biology, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Neuroprotection of Interleukin-6 Against NMDA-Induced Apoptosis and Its Signal-Transduction Mechanisms - Zhan Liu; Yi-Hua Qiu; Bing Li; Song-Hua Ma; Yu-Ping Peng (Neurotoxicity Research, 2011)

Twenty-four polymorphic microsatellite markers from spotted barbell (Hemibarbus maculates) - Jun-Jie Zhu; Shi-Li Liu; Ke-Yi Ma; Jia-Le Li; Qing-Ping Lian (Conservation Genetics Resources, 2011)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Alleviation of ovariectomy-induced osteoporosis in rats by Panax notoginseng saponins - Yang Shen; Yong-Qi Li; Shao-Ping Li; Lin Ma; Li-Ju Ding; Hui Ji (Journal of Natural Medicines, 2010)

Isolation and characterization of an abamectin-degrading Burkholderia cepacia-like GB-01 strain - Shinawar Waseem Ali; Rong Li; Wei-you Zhou; Ji-quan Sun; Peng Guo; Ji-ping Ma; Shun-peng Li (Biodegradation, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Genetic analysis of porcine circovirus type 2 (PCV2) strains isolated between 2001 and 2009: genotype PCV2b predominate in postweaning multisystemic wasting syndrome occurrences in eastern China - Wenliang Li; Xianwei Wang; Tao Ma; Zhixin Feng; Yufeng Li; Ping Jiang (Virus Genes, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Atrazine degradation by a simple consortium of Klebsiella sp. A1 and Comamonas sp. A2 in nitrogen enriched medium - Chunyu Yang; Yang Li; Kun Zhang; Xia Wang; Cuiqing Ma; Hongzhi Tang; Ping Xu (Biodegradation, 2010)

Two novel cSNPs of weaver gene in Chinese indigenous goat and their associations with milk yield - Zhuanjian Li; Zhongqi Chen; Xianyong Lan; Liang Ma; Yujiao Qu; Yanli Liu; Mijie Li; Ping Wang; Fei Li; Hong Chen (Molecular Biology Reports, 2010)

LeY oligosaccharide upregulates DAG/PKC signaling pathway in the human endometrial cells - Yali Li; Keli Ma; Ping Sun; Shuai Liu; Huamin Qin; Zhengmei Zhu; Xiaoqi Wang; Qiu Yan (Molecular and Cellular Biochemistry, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Study on swelling model and thermodynamic structure of native konjac glucomannan - Long Li; Hui Ruan; Liu-liu Ma; Wei Wang; Ping Zhou; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Purification and characterization of a thermostable uricase from Microbacterium sp. strain ZZJ4-1 - Lei Kai; Xiao-Hang Ma; Xue-Lai Zhou; Xiao-Ming Jia; Xia Li; Kang-Ping Guo (World Journal of Microbiology and Biotechnology, 2008)

Detection of three pear viruses by multiplex RT-PCR assays with co-amplification of an internal control - Bing-Gang Ma; Jian-Xin Niu; M. Morley-Bunker; Li-Zhong Pan; Hu-Ping Zhang; Lu-Xia Zhang (Australasian Plant Pathology, 2008)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Identification of a New Gene Encoding EPSPS with High Glyphosate Resistance from the Metagenomic Library - Dan Jin; Wei Lu; Shuzhen Ping; Wei Zhang; Jian Chen; Baoqing Dun; Ruiqiang Ma; Zhonglin Zhao; Jiying Sha; Liang Li; Zhirong Yang; Ming Chen; et al. (Current Microbiology, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Overexpression of the Na+/H+ antiporter gene from Suaeda salsa confers cold and salt tolerance to transgenic Arabidopsis thaliana - Jinyao Li; Gangqiang Jiang; Ping Huang; Ji Ma; Fuchun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)

Yanji city orientation and industry development towards 21st century - Ping-yu Zhang; Yan-ji Ma; Yan-xia Zhao; Li-li Pan (Chinese Geographical Science, 2001)